Polyimide composition, resin film, laminate, cover film, copper foil with resin, metal-clad laminate, and circuit board
By using high-content dimer diamine and aromatic condensed phosphate in thermoplastic resins, the dielectric properties and flame retardant properties of aliphatic thermoplastic resins are improved, and the shortcomings in the prior art under high-speed signal transmission and high-frequency environments are solved, and more efficient signal transmission is achieved.
Patent Information
- Application Number
- CN202510087660.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2019-12-27
- Filing Date
- 2020-10-23
- Publication Date
- 2025-04-29
AI Technical Summary
The existing aliphatic thermoplastic resins have shortcomings in flame retardancy and dielectric properties, and it is difficult to meet the needs of high-speed signal transmission and high-frequency.
The dielectric properties are improved by adding 40 mol% or more of the dimer diamine composition to the resin and adding aromatic condensation phosphate, silica particles or liquid crystalline polymer filler.
The dielectric properties and flexibility of the resin composition and resin film are improved, and are suitable for electronic devices for high-speed signal transmission, especially in high-frequency environments to exhibit lower dielectric loss tangents.
Smart Images

Figure BDA0005250602090000031 
Figure BDA0005250602090000061 
Figure BDA0005250602090000131
Abstract
Description
[0001] The present invention is a divisional application of the invention patent application with application number 202080069299.X filed on October 23, 2020 and the invention name "Resin composition, resin film, laminate, cover film, copper foil with resin, metal-clad laminate and circuit substrate". This application claims priority based on Japanese Patent Application No. 2019-196671 filed in Japan on October 29, 2019, and Japanese Patent Application No. 2019-238107 and Japanese Patent Application No. 2019-238108 filed in Japan on December 27, 2019, and all the contents of the above applications are cited herein. Technical Field
[0002] The present invention relates to a resin composition which is effectively used as an adhesive in a circuit substrate such as a printed wiring board, and a resin film, a laminate, a coverlay film, a copper foil with a resin, a metal-clad laminate and a circuit substrate using the same. Background Art
[0003] In recent years, with the development of miniaturization, lightness and space saving of electronic equipment, the demand for flexible printed circuits (FPC) that are thin, light, flexible and have excellent durability even when bent repeatedly has increased. FPC can be installed three-dimensionally and with high density even in a limited space, so its use has expanded to wiring of movable parts of electronic equipment such as hard disk drives (HDD), digital video disks (DVD), mobile phones, etc., or parts such as cables and connectors.
[0004] In addition to the above-mentioned high density, the high performance of equipment is also developing, so it is also necessary to cope with the high frequency of transmission signals. In information processing or information communication, efforts are made to increase the transmission frequency in order to transmit and process large amounts of information, and printed circuit board materials are required to reduce transmission losses by thinning the insulation layer and improving the dielectric properties of the insulation layer. In the future, FPCs or adhesives that are required to cope with high frequencies will have to reduce transmission losses.
[0005] For example, in millimeter wave transmission, which is one of the 5G transmissions, a direct conversion method is being studied in which the millimeter wave flows directly through the FPC connecting the antenna and the substrate. The millimeter wave band is a higher frequency than the existing communication frequency, so the dielectric loss in the transmission loss becomes larger, so it is more important to improve the dielectric properties of the insulating resin layer. As a technology for improving the dielectric properties of the insulating resin layer of the circuit substrate, it is proposed to mix liquid crystal polymer particles in a thermoplastic resin or a thermosetting resin (Patent Document 1). Among them, there are no embodiments other than epoxy resin in Patent Document 1, and no detailed research has been conducted on thermoplastic resins. In addition, it is proposed to reduce the thermal expansion coefficient and the relative dielectric constant by mixing silica particles in a polyimide resin used as an insulating resin layer of a circuit substrate (Patent Document 2, Patent Document 3).
[0006] And say, as the technology relevant with the adhesive layer with polyimide as main component, propose to apply the following cross-linked polyimide resin to the adhesive layer of cover film, described cross-linked polyimide resin is to make the diamine compound derived from aliphatic diamines such as dimer acid (dimer fatty acid) as the polyimide of raw material, and react with amino compound with at least two primary amino groups as functional group and obtain (for example, patent documentation 4).In addition, propose to apply the resin composition with thermosetting resin and cross-linking agent such as this polyimide and epoxy resin to copper-clad laminate (for example, patent documentation 5).In addition, also propose to take into account low dielectric loss tangent and flame retardancy (patent documentation 6) by mixing metal salt of organic phosphine acid in the polyimide using dimer acid type diamine.But, in patent documentation 4~patent documentation 6, about the influence of by-products other than dimer diamine derived from dimer acid contained in raw material, no consideration is made.
[0007] It is known that dimer acid is a dimerized fatty acid obtained by using natural fatty acids such as soybean oil fatty acid, tall oil fatty acid, rapeseed oil fatty acid, and oleic acid, linoleic acid, linolenic acid, erucic acid, etc. obtained by refining these acids as raw materials and subjecting them to a Diels-Alder reaction. Polyacid compounds derived from dimer acids can be obtained as raw material fatty acids or a composition of trimerized or higher fatty acids (for example, Patent Document 7).
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent No. 6295013
[0011] Patent Document 2: Japanese Patent Application Publication No. 2001-185853
[0012] Patent Document 3: Japanese Patent Application Publication No. 2018-012747
[0013] Patent Document 4: Japanese Patent Application Publication No. 2013-1730
[0014] Patent Document 5: Japanese Patent Application Publication No. 2017-119361
[0015] Patent Document 6: Japanese Patent No. 6267509
[0016] Patent Document 7: Japanese Patent Application Publication No. 2017-137375 Summary of the invention
[0017] Problems to be solved by the invention
[0018] Although thermoplastic resins such as polyimide (hereinafter sometimes referred to as "aliphatic thermoplastic resins") using aliphatic diamine compounds such as dimer diamine as raw materials have room for improvement in flame retardancy, they have low dielectric loss tangent and flexibility, and the cross-linked resin is a material that has both heat resistance and adhesion. Therefore, aliphatic thermoplastic resins are expected to be used as a material for high-speed transmission FPCs that will increase in usage due to the popularization of 5G communications. On the other hand, the frequency of signals flowing through FPCs is expected to be higher in the future, so a material based on aliphatic thermoplastic resins and having good dielectric properties is required.
[0019] In addition, as a method for controlling the physical property of a resin using polyimide as a main component, it is important to control the molecular weight of a polyamic acid or polyimide as a precursor of polyimide. However, when dimer diamine is used as a raw material, it is used in a state containing by-products other than the dimer diamine derived from dimer acid. Such by-products, in addition to being difficult to control the molecular weight of polyimide, have an impact on the dielectric properties or its humidity dependence under the frequency of a wide region.
[0020] Therefore, the first object of the present invention is to provide a resin composition and a resin film that can cope with the high frequency of electronic equipment by further improving the dielectric properties of an aliphatic thermoplastic resin. In addition, the second object of the present invention is to provide a resin composition and a resin film that can cope with the high frequency of electronic equipment by improving the dielectric properties while using a dimer diamine as a raw material.
[0021] Technical means of solving problems
[0022] The resin composition of the present invention contains the following components (A) and (B);
[0023] (A) a thermoplastic resin containing a structural unit derived from a diamine component, wherein the diamine component contains a dimer diamine composition having as a main component a dimer diamine in which both terminal carboxylic acid groups of a dimer acid are substituted with primary aminomethyl groups or amino groups in an amount of 40 mol % or more based on all diamine components,
[0024] and
[0025] (B) at least one selected from aromatic condensed phosphate esters, silica particles, and liquid crystalline polymer fillers.
[0026] In the resin composition of the present invention, the component (A) may be a polyimide obtained by reacting a tetracarboxylic anhydride component with a diamine component containing 40 mol % or more of the dimer diamine composition relative to all diamine components, and the component (B) may be the aromatic condensed phosphate ester. In the case, the weight ratio of the component (B) to the component (A) may be in the range of 0.05 to 0.7, preferably in the range of 0.2 to 0.5. In addition, the weight ratio of phosphorus derived from the aromatic condensed phosphate ester of the component (B) to the component (A) may be in the range of 0.01 to 0.1. Furthermore, the weight ratio of phosphorus derived from the aromatic condensed phosphate ester of the component (B) to the dimer diamine composition in the component (A) may be in the range of 0.01 to 0.15.
[0027] The resin composition of the present invention may further contain an amino compound having at least two primary amino groups as functional groups.
[0028] In the resin composition of the present invention, the (A) component may be a polyamic acid or polyimide formed by reacting a tetracarboxylic anhydride component with a diamine component containing more than 40 mol% of the dimer diamine composition relative to all diamine components, and the (B) component may be a silica particle having a white silica crystal phase or a quartz crystal phase. In the case, relative to the total of the (A) component (wherein the polyamic acid is converted into an imidized polyimide) and the (B) component, the (B) component may be in the range of 5 wt % to 60 wt %. In addition, in the silica particles of the (B) component, the total area of the peaks of the white silica crystal phase and the quartz crystal phase in the range of 2θ=10° to 90° of the X-ray diffraction analysis spectrum of CuKα rays relative to the total area of all peaks from SiO2 may be more than 20 wt %. Furthermore, in the silica particles of the component (B), the average particle size D at which the cumulative value in the frequency distribution curve obtained by volume-based particle size distribution measurement using a laser diffraction scattering method becomes 50% is 50 It can be in the range of 6 μm to 20 μm.
[0029] In the resin composition of the present invention, the (A) component may be a polyimide formed by reacting a tetracarboxylic anhydride component with a diamine component containing more than 40 mol% of the dimer diamine composition relative to all diamine components, and the (B) component may be the liquid crystalline polymer filler. In the case, relative to the total of the (A) component and the (B) component, the (B) component may be in the range of 15% by volume to 50% by volume. In addition, when the dielectric loss tangent of the (A) component at 10 GHz is set to Dfa and the dielectric loss tangent of the liquid crystalline polymer filler of the (B) component at 10 GHz is set to Dfb, Dfb may be less than 0.0019, and may be Dfa>Dfb. In addition, relative to 100% by weight of the non-volatile organic compound component of the resin composition, 15% by weight to 30% by weight of a phosphorus flame retardant may be further added.
[0030] In the resin composition of the present invention, the component (A) may contain 90 mol parts or more of tetracarboxylic anhydride represented by the following general formula (1) and / or general formula (2) in total, relative to 100 mol parts of the tetracarboxylic anhydride component.
[0031] [Chemistry 1]
[0032]
[0033] In the general formula (1), X represents a single bond or a divalent group selected from the following formula; in the general formula (2), the cyclic part represented by Y represents a cyclic saturated hydrocarbon group selected from a four-membered ring, a five-membered ring, a six-membered ring, a seven-membered ring or an eight-membered ring.
[0034] [Chemistry 2]
[0035] -CO-, -SO2-, -O-,
[0036] -C(CF3)2-,
[0037] -COO- or -COO-Z-OCO-
[0038] In the above formula, Z represents -C6H4-, -(CH2)n- or -CH2-CH(-OC(=O)-CH3)-CH2-, and n represents an integer of 1 to 20.
[0039] The resin film of the present invention is a resin film comprising a thermoplastic resin layer, and
[0040] Contains the following components (A) and (B);
[0041] (A) a thermoplastic resin containing a structural unit derived from a diamine component, wherein the diamine component contains a dimer diamine composition having as a main component a dimer diamine in which both terminal carboxylic acid groups of a dimer acid are substituted with primary aminomethyl groups or amino groups in an amount of 40 mol % or more based on all diamine components,
[0042] and
[0043] (B) at least one selected from aromatic condensed phosphate esters, silica particles, and liquid crystalline polymer fillers.
[0044] The thickness of the resin film of the present invention can be in the range of 15 μm to 100 μm.
[0045] In the resin film of the present invention, when the component (B) includes silica particles having a cristobalite crystal phase or a quartz crystal phase, the content thereof may be in the range of 3 to 41 volume % based on the total of the components (A) and (B).
[0046] In the resin film of the present invention, when the component (B) contains the liquid crystalline polymer filler, the content thereof may be in the range of 15 to 40 volume % based on the total of the components (A) and (B).
[0047] The laminated body of the present invention comprises a substrate and an adhesive layer laminated on at least one surface of the substrate, wherein the adhesive layer includes the resin film.
[0048] The cover film of the present invention comprises a cover film material layer and an adhesive layer laminated on the cover film material layer, wherein the adhesive layer includes the resin film.
[0049] The copper foil with resin of the present invention is obtained by laminating an adhesive layer and a copper foil, wherein the adhesive layer includes the resin film.
[0050] The metal-clad laminate of the present invention comprises an insulating resin layer and a metal layer laminated on at least one surface of the insulating resin layer, wherein at least one layer of the insulating resin layer includes the resin film.
[0051] The circuit board of the present invention is obtained by subjecting the metal layer of the metal-clad laminate to wiring processing.
[0052] Effects of the Invention
[0053] The resin composition of the present invention contains components (A) and (B), so the resin film formed using the composition has excellent dielectric properties and flexibility derived from dimer diamine, and has dielectric properties further improved by the formulation of component (B). Therefore, the resin composition and resin film of the present invention can be particularly preferably used as a circuit substrate material such as FPC in electronic devices requiring high-speed signal transmission. DETAILED DESCRIPTION
[0054] Hereinafter, embodiments of the present invention will be described.
[0055] The resin composition according to one embodiment of the present invention contains the following components (A) and (B);
[0056] (A) a thermoplastic resin containing a structural unit derived from a diamine component, wherein the diamine component contains a dimer diamine composition having as a main component a dimer diamine in which both terminal carboxylic acid groups of a dimer acid are substituted with primary aminomethyl groups or amino groups in an amount of 40 mol % or more based on all diamine components,
[0057] and
[0058] (B) at least one selected from aromatic condensed phosphate esters, silica particles, and liquid crystalline polymer fillers.
[0059] [(A) component: thermoplastic resin]
[0060] The so-called thermoplastic resin of component (A) refers to a resin containing a structural unit derived from a diamine component and having a maximum value of a loss tangent (tan δ) of less than 200°C measured using a dynamic viscoelasticity measuring device (dynamic mechanical analyzer (DMA)), wherein the diamine component contains a dimer diamine composition as a main component of which the two terminal carboxylic acid groups of the dimer acid are substituted with a primary aminomethyl or amino group at 40 mol% or more relative to all diamine components. Thus, as a thermoplastic resin, there can be cited: a thermoplastic polyimide using a diamine component containing 40 mol% or more of a dimer diamine composition as a raw material, a polyamic acid as a precursor thereof, a thermoplastic bismaleimide resin, a thermoplastic epoxy resin, a thermoplastic polyamide resin, and hardened materials thereof. These thermoplastic resins can be formulated in combination of two or more. Among these thermoplastic resins, more preferred are thermoplastic polyimides obtained by imidizing a precursor polyamic acid obtained by reacting a tetracarboxylic anhydride component with a diamine component (hereinafter sometimes referred to as "DDA-based thermoplastic polyimide"), and crosslinked cured products thereof, wherein the diamine component contains a dimer diamine composition having as a main component a dimer diamine in which both terminal carboxylic acid groups of a dimer acid are substituted with primary aminomethyl groups or amino groups in an amount of 40 mol % or more relative to all diamine components.
[0061] Hereinafter, DDA-based thermoplastic polyimide is listed as a representative example of the thermoplastic resin and described in detail.
[0062] The so-called "thermoplastic polyimide" is generally a polyimide whose glass transition temperature (Tg) can be clearly confirmed, but in the present invention, it means: a polyimide having a storage elastic modulus of 1.0×10 8 Pa or more, and the storage elastic coefficient at 300°C is less than 3.0×10 7 In addition, the so-called "non-thermoplastic polyimide" is generally a polyimide that does not soften even when heated and exhibits adhesiveness, but in the present invention, it means: a polyimide having a storage elastic modulus of 1.0×10 9 Pa and the storage elastic coefficient at 300°C is 3.0×10 8 Pa or more polyimide.
[0063] <DDA-based thermoplastic polyimide>
[0064] DDA-based thermoplastic polyimide is an aliphatic thermoplastic polyimide, rich in flexibility, even in the case of adding a large amount of liquid crystal polymer fillers, it also has sufficient toughness, and has a high ability to maintain its shape when forming a resin film. Therefore, the content of the DDA-based thermoplastic polyimide in the (A) component is preferably 60% by weight or more, more preferably 70% by weight or more, and most preferably 80% by weight or more. If the content of the DDA-based thermoplastic polyimide in the (A) component is less than 60% by weight, the toughness of the thermoplastic resin is reduced, and the film retention when forming a resin film is reduced.
[0065] The DDA-based thermoplastic polyimide contains a tetracarboxylic acid residue derived from a tetracarboxylic anhydride as a raw material and a diamine residue derived from a diamine compound as a raw material. By reacting the tetracarboxylic anhydride and the diamine compound as raw materials in substantially equimolar amounts, the type and amount of the tetracarboxylic acid residue and the diamine residue contained in the DDA-based thermoplastic polyimide can be made to substantially correspond to the type and amount of the raw materials.
[0066] (Tetracarboxylic anhydride component)
[0067] DDA-based thermoplastic polyimide can use tetracarboxylic anhydride generally used in thermoplastic polyimide as a raw material without particular limitation, and preferably contains a total of 90 mol% or more of tetracarboxylic anhydride represented by the following general formula (1) and / or general formula (2) relative to all tetracarboxylic anhydride components. In other words, DDA-based thermoplastic polyimide preferably contains a total of 90 mol% or more of tetracarboxylic acid residues derived from tetracarboxylic anhydride represented by the following general formula (1) and / or general formula (2) relative to 100 mol parts of all tetracarboxylic acid residues. By containing a total of 90 mol% or more of tetracarboxylic acid residues derived from tetracarboxylic anhydride represented by the following general formula (1) and / or general formula (2) relative to 100 mol parts of tetracarboxylic acid residues, it is easy to achieve a balance between the softness and heat resistance of the DDA-based thermoplastic polyimide and is preferred. When the total amount of tetracarboxylic acid residues derived from tetracarboxylic anhydride represented by the following general formula (1) and / or general formula (2) is less than 90 parts by mole, the solvent solubility of the DDA-based thermoplastic polyimide tends to decrease.
[0068] [Chemistry 3]
[0069]
[0070] In the general formula (1), X represents a single bond or a divalent group selected from the following formula; in the general formula (2), the cyclic part represented by Y represents a cyclic saturated hydrocarbon group selected from a four-membered ring, a five-membered ring, a six-membered ring, a seven-membered ring or an eight-membered ring.
[0071] [Chemistry 4]
[0072] -CO-, -SO2-, -O-,
[0073] -C(CF3)2-,
[0074] -COO- or -COO-Z-OCO-
[0075] In the above formula, Z represents -C6H4-, -(CH2)n- or -CH2-CH(-OC(=O)-CH3)-CH2-, and n represents an integer of 1 to 20.
[0076] Examples of the tetracarboxylic anhydride represented by the general formula (1) include 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA), 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride (DSDA), 4,4'-oxydiphthalic anhydride (ODPA), 4,4'-(hexafluoroisopropylidene)diphthalic anhydride (6FDA), 2,2-bis[4-(3,4-dicarboxyphenoxy)phenyl]propane dianhydride (BPADA), p-phenylenebis(trimellitic acid monoester anhydride) (TAHQ), ethylene glycol bis(trimellitic acid monoester anhydride) (TMEG), etc. Among these, 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA) is particularly preferred. When BTDA is used, the carbonyl group (ketone group) contributes to the adhesion, thus suppressing the decrease in peel strength when adding a liquid crystal polymer filler as the (B) component, and improving the adhesion of the DDA-based thermoplastic polyimide. In addition, the ketone group present in the molecular skeleton of BTDA reacts with the amino group of the amino compound formed by crosslinking described later to form a C=N bond, which easily shows the effect of improving heat resistance. From this point of view, it is preferable to contain 50 mol parts or more, more preferably 60 mol parts or more of the tetracarboxylic acid residue derived from BTDA relative to 100 mol parts of the tetracarboxylic acid residue.
[0077] Examples of the tetracarboxylic anhydride represented by the general formula (2) include 1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,2,3,4-cyclopentanetetracarboxylic dianhydride, 1,2,4,5-cyclohexanetetracarboxylic dianhydride, 1,2,4,5-cycloheptanetetracarboxylic dianhydride, and 1,2,5,6-cyclooctanetetracarboxylic dianhydride.
[0078] The DDA-based thermoplastic polyimide may contain a tetracarboxylic acid residue derived from an acid anhydride other than the tetracarboxylic acid anhydride represented by the general formula (1) and the general formula (2) within a range that does not impair the effects of the invention. Such a tetracarboxylic acid residue is not particularly limited, and examples thereof include pyromellitic acid dianhydride, 2,3',3,4'-biphenyltetracarboxylic acid dianhydride, 2,2',3,3'-benzophenonetetracarboxylic acid dianhydride or 2,3,3',4'-benzophenonetetracarboxylic acid dianhydride, 2,3',3,4'-diphenylethertetracarboxylic acid dianhydride, bis(2,3-dicarboxyphenyl)ether dianhydride, 3,3",4,4"-triphenylenetetracarboxylic acid dianhydride, 2,3,3",4"-triphenylenetetracarboxylic acid dianhydride or 2,2",3,3"-triphenylenetetracarboxylic acid dianhydride, 2,2-diphenylenetetracarboxylic acid dianhydride. (2,3-dicarboxyphenyl)-propane dianhydride or 2,2-bis(3,4-dicarboxyphenyl)-propane dianhydride, bis(2,3-dicarboxyphenyl)methane dianhydride or bis(3,4-dicarboxyphenyl)methane dianhydride, bis(2,3-dicarboxyphenyl)sulfone dianhydride or bis(3,4-dicarboxyphenyl)sulfone dianhydride, 1,1-bis(2,3-dicarboxyphenyl)ethane dianhydride or 1,1-bis(3,4-dicarboxyphenyl)ethane dianhydride, 1,2,7,8-phenanthrene-tetracarboxylic dianhydride, 1,2,6,7-phenanthrene-tetracarboxylic dianhydride or 1,2,9,10-phenanthrene-tetracarboxylic dianhydride carboxylic acid dianhydride, 2,3,6,7-anthracenetetracarboxylic dianhydride, 2,2-bis(3,4-dicarboxyphenyl)tetrafluoropropane dianhydride, 1,2,5,6-naphthalenetetracarboxylic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride, 2,3,6,7-naphthalenetetracarboxylic dianhydride, 4,8-dimethyl-1,2,3,5,6,7-hexahydronaphthalene-1,2,5,6-tetracarboxylic dianhydride, 2,6-dichloronaphthalene-1,4,5,8-tetracarboxylic dianhydride or 2,7-dichloronaphthalene-1,4,5,8-tetracarboxylic dianhydride, 2,3,6,7-(or 1,4,5,8-)tetrachloro A tetracarboxylic acid residue derived from an aromatic tetracarboxylic acid dianhydride such as naphthalene-1,4,5,8-(or 2,3,6,7-)tetracarboxylic dianhydride, 2,3,8,9-perylene-tetracarboxylic dianhydride, 3,4,9,10-perylene-tetracarboxylic dianhydride, 4,5,10,11-perylene-tetracarboxylic dianhydride or 5,6,11,12-perylene-tetracarboxylic dianhydride, pyrazine-2,3,5,6-tetracarboxylic dianhydride, pyrrolidine-2,3,4,5-tetracarboxylic dianhydride, thiophene-2,3,4,5-tetracarboxylic dianhydride, or 4,4'-bis(2,3-dicarboxyphenoxy)diphenylmethane dianhydride.
[0079] (Diamine component)
[0080] The DDA-based thermoplastic polyimide uses as a raw material a diamine component containing 40 mol% or more, more preferably 60 mol% or more of a dimer diamine composition relative to all diamine components. By containing the dimer diamine composition in such an amount, the dielectric properties of the polyimide can be improved, the thermocompression bonding properties can be improved by lowering the glass transition temperature (lowering Tg) of the polyimide, and the internal stress can be relaxed by lowering the elastic modulus.
[0081] (Dimer diamine composition)
[0082] The dimer diamine composition contains the following component (a) as a main component, and the amounts of the component (b) and the component (c) are controlled.
[0083] (a) dimer diamine;
[0084] The dimer diamine as component (a) refers to a diamine in which the two terminal carboxylic acid groups (-COOH) of the dimer acid are substituted with primary aminomethyl groups (-CH2-NH2) or amino groups (-NH2). Dimer acid is a known dibasic acid obtained by intermolecular polymerization of unsaturated fatty acids. Its industrial production process has been roughly standardized in the industry, and is obtained by dimerizing unsaturated fatty acids with carbon numbers of 11 to 22 using clay catalysts, etc. The industrially obtained dimer acid is mainly a dibasic acid with carbon number 36 obtained by dimerizing unsaturated fatty acids with carbon number 18 such as oleic acid, linolenic acid, and linolenic acid, and contains any amount of monomer acid (carbon number 18), trimer acid (carbon number 54), and other polymerized fatty acids with carbon number 20 to 54, depending on the degree of purification. In addition, after the dimerization reaction, double bonds remain, but in the present invention, dimer acids are also included in the present invention, which are further hydrogenated to reduce the degree of unsaturation. The dimer diamine as the component (a) can be defined as a diamine compound obtained by substituting the terminal carboxylic acid group of a dibasic acid compound having a carbon number of 18 to 54, preferably 22 to 44, with a primary aminomethyl group or an amino group.
[0085] As the characteristic of dimer diamine, the characteristic derived from dimer acid skeleton can be given. That is, dimer diamine is a huge molecule aliphatic with a molecular weight of about 560 to 620, so the molar volume of the molecule can be increased, and the polar group of DDA-based thermoplastic polyimide can be relatively reduced. It is believed that the characteristics of such dimer acid-type diamines help to suppress the reduction of the heat resistance of DDA-based thermoplastic polyimide, while reducing relative dielectric constant and dielectric loss tangent, and improving dielectric properties. In addition, due to having two hydrophobic chains with two freely movable carbon numbers of 7 to 9 and two chain aliphatic amino groups with a length close to carbon number 18, it is not only possible to give flexibility to DDA-based thermoplastic polyimide, but also DDA-based thermoplastic polyimide is set to an asymmetric chemical structure or a non-planar chemical structure, so it is believed that low dielectric constant can be achieved.
[0086] The dimer diamine composition is preferably one in which the content of the dimer diamine as the component (a) is increased to 96% by weight or more, preferably 97% by weight or more, and more preferably 98% by weight or more by a purification method such as molecular distillation. By setting the content of the dimer diamine as the component (a) to 96% by weight or more, the expansion of the molecular weight distribution of the DDA-based thermoplastic polyimide can be suppressed. Furthermore, if technically feasible, it is most preferred that the entirety (100% by weight) of the dimer diamine composition includes the dimer diamine as the component (a).
[0087] (b) a monoamine compound obtained by substituting the terminal carboxylic acid group of a monobasic acid compound having 10 to 40 carbon atoms with a primary aminomethyl group or an amino group;
[0088] The monoacid compound having a carbon number of 10 to 40 is a mixture of a monobasic unsaturated fatty acid having a carbon number of 10 to 20 derived from a raw material of dimer acid and a monoacid compound having a carbon number of 21 to 40, which is a byproduct when producing dimer acid. The monoamine compound is obtained by substituting the terminal carboxylic acid group of these monoacid compounds with a primary aminomethyl group or an amino group.
[0089] The monoamine compound as component (b) is a component that suppresses the increase in molecular weight of polyimide. During the polymerization of polyamic acid or polyimide, the monofunctional amino group of the monoamine compound reacts with the terminal anhydride group of polyamic acid or polyimide, thereby sealing the terminal anhydride group and suppressing the increase in molecular weight of polyamic acid or polyimide.
[0090] (c) an amine compound obtained by substituting a terminal carboxylic acid group of a polyacid compound having a hydrocarbon group in the range of 41 to 80 carbon atoms with a primary aminomethyl group or an amino group (except the dimer diamine);
[0091] The polybasic acid compound having a hydrocarbon group in the range of 41 to 80 carbon atoms is a polybasic acid compound having as a main component a tribasic acid compound in the range of 41 to 80 carbon atoms, which is a byproduct when producing dimer acid. In addition, a polymerized fatty acid other than the dimer acid in the range of 41 to 80 carbon atoms may be contained. The amine compound is obtained by substituting the terminal carboxylic acid group of these polybasic acid compounds with a primary aminomethyl group or an amino group.
[0092] The amine compound as component (c) is a component that promotes the increase in the molecular weight of the polyimide. The triamine body derived from trimer acid as the main component of the trifunctional or higher amino group reacts with the terminal acid anhydride group of the polyamic acid or polyimide to increase the molecular weight of the polyimide sharply. In addition, the amine compound derived from the polymerized fatty acid other than the dimer acid having 41 to 80 carbon atoms also increases the molecular weight of the polyimide and becomes the cause of the gelation of the polyamic acid or polyimide.
[0093] When the dimer diamine composition is quantitatively measured by gel permeation chromatography (GPC), a sample treated with acetic anhydride and pyridine is used to easily confirm the peak start, peak top, and peak end of each component of the dimer diamine composition, and cyclohexanone is used as an internal standard substance. The sample prepared in the above manner is used to quantify each component using the area percentage of the chromatogram of GPC. The peak start and peak end of each component can be used as the minimum value of each peak curve and used as a reference to calculate the area percentage of the chromatogram.
[0094] In addition, in the dimer diamine composition used in the present invention, the total content of component (b) and component (c) is preferably 4% or less, preferably less than 4%, in terms of area percentage of the chromatogram obtained by GPC measurement. By setting the total content of component (b) and component (c) to 4% or less, the spread of the molecular weight distribution of the polyimide can be suppressed.
[0095] In addition, the area percentage of the chromatogram of the component (b) is preferably 3% or less, more preferably 2% or less, and further preferably 1% or less. By setting it to such a range, the decrease in the molecular weight of the polyimide can be suppressed, and the range of the molar ratio of the tetracarboxylic anhydride component and the diamine component can be expanded. Furthermore, the component (b) may not be included in the dimer diamine composition.
[0096] In addition, the area percentage of the chromatogram of the component (c) is preferably 2% or less, preferably 1.8% or less, and more preferably 1.5% or less. By setting it to such a range, the molecular weight of the polyimide can be suppressed from increasing sharply, and the dielectric loss tangent of the resin film can be suppressed from rising at a frequency in a wide region. Furthermore, the component (c) may not be included in the dimer diamine composition.
[0097] In addition, when the ratio (b / c) of the area percentage of the chromatogram of component (b) and component (c) is 1 or more, the molar ratio of the tetracarboxylic anhydride component and the diamine component (tetracarboxylic anhydride component / diamine component) is preferably set to 0.97 or more and less than 1.0. By setting such a molar ratio, it is easier to control the molecular weight of the polyimide.
[0098] In addition, when the ratio (b / c) of the area percentage of the chromatogram of component (b) and component (c) is less than 1, the molar ratio of the tetracarboxylic anhydride component and the diamine component (tetracarboxylic anhydride component / diamine component) is preferably set to 0.97 or more and 1.1 or less. By setting such a molar ratio, it is easier to control the molecular weight of the polyimide.
[0099] The dimer diamine composition used in the present invention is preferably refined for the purpose of reducing the components other than the dimer diamine as (a) component. As a refining method, there is no particular limitation, preferably a known method such as distillation or precipitation refining. The dimer diamine composition before refining can be obtained with a commercial product, for example, PRIAMINE 1073 (trade name) manufactured by Croda Japan, PRIAMINE 1074 (trade name) manufactured by Croda Japan, PRIAMINE 1075 (trade name) manufactured by Croda Japan, etc.
[0100] Examples of diamine compounds other than the dimer diamine used in the DDA-based thermoplastic polyimide include aromatic diamine compounds and aliphatic diamine compounds. Specific examples thereof include 1,4-diaminobenzene (p-PDA; p-phenylenediamine), 2,2'-dimethyl-4,4'-diaminobiphenyl (m-TB), 2,2'-n-propyl-4,4'-diaminobiphenyl (m-NPB), 4-aminophenyl-4'-aminobenzoate (APAB), 2,2-bis-[4-(3-aminophenoxy)phenyl]propane, bis[4-(3-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)]biphenyl, bis[1-(3-aminophenoxy)]biphenyl, bis[4-(3-aminophenoxy)phenyl] ]methane, bis[4-(3-aminophenoxy)phenyl]ether, bis[4-(3-aminophenoxy)]benzophenone, 9,9-bis[4-(3-aminophenoxy)phenyl]fluorene, 2,2-bis-[4-(4-aminophenoxy)phenyl]hexafluoropropane, 2,2-bis-[4-(3-aminophenoxy)phenyl]hexafluoropropane, 3,3'-dimethyl-4,4'-diaminobiphenyl, 4,4'-methylenebis-o-toluidine, 4,4'-methylenebis-2,6-dimethylaniline, 4,4'-methylenebis-2,6-diethylaniline, 3,3'-diaminodiphenylethane, 3,3'-diaminobiphenyl, 3,3'-dimethoxybenzidine, 3,3"-diamino-p-terphenyl, 4,4'-[1,4-phenylenebis(1-methylethylidene)]dianiline, 4,4'-[1,3-phenylenebis(1-methylethylidene)]dianiline, bis(p-aminocyclohexyl)methane, bis(p-β-amino-tert-butylphenyl) ether, bis(p-β-methyl-δ-aminopentyl)benzene, p-bis(2-methyl-4-aminopentyl)benzene, p-bis(1,1-dimethyl-5-aminopentyl)benzene, 1,5-diaminonaphthalene, 2,6-diaminonaphthalene, 2,4-diaminonaphthalene (β-amino-tert-butyl)toluene, 2,4-diaminotoluene, m-xylene-2,5-diamine, p-xylene-2,5-diamine, m-phenylenediamine, p-phenylenediamine, 2,6-diaminopyridine, 2,5-diaminopyridine, 2,5-diamino-1,3,4-oxadiazole, piperazine, 2'-methoxy-4,4'-diaminobenzanilide, 4,4'-diaminobenzanilide, 1,3-bis[2-(4-aminophenyl)-2-propyl]benzene, 6-amino-2-(4-aminophenoxy)benzoxazole, 1,3-bis(3-aminophenoxy)benzene and other diamine compounds.
[0101] DDA-based thermoplastic polyimide can be manufactured by reacting the tetracarboxylic anhydride component with a diamine component in a solvent to generate a polyamic acid and then heating the polyamic acid for ring closure. For example, the tetracarboxylic anhydride component and the diamine component are dissolved in an organic solvent in approximately equimolar amounts, and the polymerization reaction is carried out by stirring for 30 minutes to 24 hours at a temperature in the range of 0°C to 100°C, thereby obtaining a polyamic acid as a precursor of the polyimide. During the reaction, the reaction components are dissolved in a manner such that the generated precursor becomes within the range of 5% by weight to 50% by weight, preferably within the range of 10% by weight to 40% by weight in the organic solvent. As the organic solvent used in the polymerization reaction, for example, N, N-dimethylformamide (DMF), N, N-dimethylacetamide (DMAc), N, N-diethylacetamide, N-methyl-2-pyrrolidone (NMP), 2-butanone, dimethyl sulfoxide (DMSO), hexamethylphosphoramide, N-methylcaprolactam, dimethyl sulfate, cyclohexanone, methylcyclohexane, dioxane, tetrahydrofuran, diethylene glycol dimethyl ether (diglyme), triethylene glycol dimethyl ether (triglyme), methanol, ethanol, benzyl alcohol, cresol, etc. can be listed. These solvents can also be used in combination of two or more, and aromatic hydrocarbons such as xylene and toluene can also be used in combination. In addition, as the amount of such an organic solvent, there is no particular limitation, and it is preferably adjusted to the concentration of the polyamic acid solution obtained by the polymerization reaction to be 5% by weight to 50% by weight.
[0102] The synthesized polyamic acid is usually advantageously used as a reaction solvent solution, and can be concentrated, diluted or replaced with other organic solvents as needed. In addition, polyamic acid is generally advantageously used due to its excellent solvent solubility. The viscosity of the solution of polyamic acid is preferably within the range of 500cps to 100,000cps. If it deviates from the range, it is easy to produce uneven thickness, stripes and other undesirable conditions in the film when a coating operation is performed using a coating machine or the like.
[0103] The method for imidizing the polyamic acid to form the polyimide is not particularly limited, and for example, a heat treatment such as heating in the solvent at a temperature condition in the range of 80° C. to 400° C. for 1 to 24 hours can be preferably adopted. In addition, the temperature can be heated at a fixed temperature condition or the temperature can be changed in the middle of the step.
[0104] In the DDA-based thermoplastic polyimide, by selecting the types of the tetracarboxylic anhydride component and the diamine component, or the respective molar ratios when two or more tetracarboxylic anhydride components or diamine components are used, the dielectric properties, thermal expansion coefficient, tensile elastic coefficient, glass transition temperature, etc. can be controlled. In addition, in the DDA-based thermoplastic polyimide, when there are a plurality of structural units of polyimide, they may exist in the form of blocks or randomly, preferably randomly.
[0105] The weight average molecular weight of DDA-based thermoplastic polyimide is preferably, for example, in the range of 10,000 to 200,000. If it is within this range, the weight average molecular weight of the polyimide can be easily controlled. In addition, for example, when used as an adhesive for FPC, the weight average molecular weight of DDA-based thermoplastic polyimide is more preferably in the range of 20,000 to 150,000, and further preferably in the range of 40,000 to 150,000. When used as an adhesive for FPC, when the weight average molecular weight of DDA-based thermoplastic polyimide is less than 20,000, there is a tendency for the fluidity resistance to deteriorate. On the other hand, if the weight average molecular weight of DDA-based thermoplastic polyimide exceeds 150,000, the viscosity increases excessively and is insoluble in the solvent, and there is a tendency to easily produce undesirable conditions such as uneven thickness and stripes of the adhesive layer during the coating operation.
[0106] The imide group concentration of the DDA-based thermoplastic polyimide is preferably 22% by weight or less, more preferably 20% by weight or less. Here, "imide group concentration" refers to the value obtained by dividing the molecular weight of the imide group (-(CO)2-N-) in the polyimide by the molecular weight of the entire structure of the polyimide. If the imide group concentration exceeds 22% by weight, the molecular weight of the resin itself becomes smaller, and the low hygroscopicity is also deteriorated due to the increase in polar groups, and Tg and elastic modulus increase.
[0107] The DDA-based thermoplastic polyimide is most preferably a fully imidized structure. Part of the polyimide may be converted into amic acid. The imidization rate can be measured by using a Fourier transform infrared spectrophotometer (commercially available product: FT / IR620 manufactured by JASCO Corporation) and using the attenuated total reflection (ATR) method to measure the infrared absorption spectrum of the polyimide film. -1 The nearby benzene ring absorber is used as a reference, based on the 1780cm -1 The absorbance derived from the expansion and contraction of C=O of the imide group was calculated.
[0108] <Cross-link formation>
[0109] When the DDA-based thermoplastic polyimide in the component (A) has a ketone group, the ketone group is reacted with an amino group of an amino compound having at least two primary amino groups as functional groups (hereinafter, sometimes referred to as "amino compound for crosslinking formation") to form a C=N bond, thereby forming a crosslinked structure. By forming a crosslinked structure, the heat resistance of the DDA-based thermoplastic polyimide can be improved. As a preferred tetracarboxylic anhydride for forming a DDA-based thermoplastic polyimide having a ketone group, for example, 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA) can be cited, and as a diamine compound, for example, aromatic diamines such as 4,4'-bis(3-aminophenoxy)benzophenone (BABP) and 1,3-bis[4-(3-aminophenoxy)benzoyl]benzene (BABB) can be cited.
[0110] In order to form a crosslinked structure, the resin composition of the present embodiment preferably comprises: the DDA-based thermoplastic polyimide in the component (A) containing BTDA residues derived from BTDA in an amount of preferably 50 mol% or more, more preferably 60 mol% or more relative to all tetracarboxylic acid residues, and an amino compound for crosslinking formation. In the present invention, the "BTDA residue" refers to a tetravalent group derived from BTDA.
[0111] As the amino compound for crosslinking formation, there can be exemplified: (I) dihydrazide compounds, (II) aromatic diamines, (III) aliphatic amines, etc. Among these, dihydrazide compounds are preferred. Aliphatic amines other than dihydrazide compounds are easy to form crosslinked structures even at room temperature, and there are concerns about the storage stability of the varnish. On the other hand, aromatic diamines need to be set to high temperature in order to form a crosslinked structure. In this way, when using dihydrazide compounds, both the storage stability of the varnish and the shortening of the curing time can be taken into account. As the dihydrazide compound, for example, dihydrazide compounds such as oxalic acid dihydrazide, malonic acid dihydrazide, succinic acid dihydrazide, glutaric acid dihydrazide, adipic acid dihydrazide, pimelic acid dihydrazide, suberic acid dihydrazide, azelaic acid dihydrazide, sebacic acid dihydrazide, dodecanedioic acid dihydrazide, maleic acid dihydrazide, fumaric acid dihydrazide, diglycolic acid dihydrazide, tartaric acid dihydrazide, malic acid dihydrazide, phthalic acid dihydrazide, isophthalic acid dihydrazide, terephthalic acid dihydrazide, 2,6-naphthoic acid dihydrazide, 4,4-bis(phenylene)dihydrazide, 1,4-naphthoic acid dihydrazide, 2,6-pyridine dihydrazide, and itaconic acid dihydrazide are preferred. The above dihydrazide compounds may be used alone or in combination of two or more.
[0112] Furthermore, the amino compounds such as (I) dihydrazide compounds, (II) aromatic diamines, and (III) aliphatic amines may be used in combination of two or more, for example, a combination of (I) and (II), a combination of (I) and (III), and a combination of (I) and (II) and (III).
[0113] In addition, from the viewpoint of making the network structure formed by crosslinking using the crosslink-forming amino compound denser, the molecular weight of the crosslink-forming amino compound used in the present invention (the weight average molecular weight when the crosslink-forming amino compound is an oligomer) is preferably 5,000 or less, more preferably 90 to 2,000, and further preferably 100 to 1,500. Among these, crosslink-forming amino compounds having a molecular weight of 100 to 1,000 are particularly preferred. If the molecular weight of the crosslink-forming amino compound is less than 90, one amino group of the crosslink-forming amino compound is limited to forming a C=N bond with the ketone group of the DDA-based thermoplastic polyimide, and the surrounding area of the remaining amino group becomes sterically bulky, so there is a tendency that the remaining amino group is not easy to form a C=N bond.
[0114] When the ketone group in the DDA-based thermoplastic polyimide in the component (A) is cross-linked with the cross-linking amino compound, the cross-linking amino compound is added to the resin solution containing the component (A) to cause the ketone group in the DDA-based thermoplastic polyimide to undergo a condensation reaction with the primary amino group of the cross-linking amino compound. Through the condensation reaction, the resin solution is cured to become a cured product. In the case, the amount of the cross-linking amino compound added is 0.004 mol to 1.5 mol, preferably 0.005 mol to 1.2 mol, more preferably 0.03 mol to 0.9 mol, and most preferably 0.04 mol to 0.6 mol, relative to 1 mol of the ketone group. Regarding the addition amount of the cross-linking amino compound such that the total primary amino group is less than 0.004 mol relative to 1 mol of keto group, since the cross-linking by the cross-linking amino compound is insufficient, there is a tendency that the heat resistance after curing is difficult to express. If the addition amount of the cross-linking amino compound exceeds 1.5 mol, the unreacted cross-linking amino compound acts as a thermoplastic agent, and there is a tendency to reduce the heat resistance of the adhesive layer.
[0115] The conditions for the condensation reaction for crosslinking formation are not particularly limited as long as the ketone group in the DDA-based thermoplastic polyimide in the component (A) reacts with the primary amino group of the amino compound for crosslinking formation to form an imine bond (C=N bond). Regarding the temperature of the heating condensation, for example, it is preferably in the range of 120°C to 220°C, and more preferably in the range of 140°C to 200°C, for the reasons of releasing the water generated by the condensation to the outside of the system, or simplifying the condensation step when the heating condensation reaction is carried out after the synthesis of the DDA-based thermoplastic polyimide in the component (A). The reaction time is preferably about 30 minutes to 24 hours. The end point of the reaction can be determined, for example, by using a Fourier transform infrared spectrophotometer (commercially available product: FT / IR620 manufactured by JASCO Corporation) to measure the infrared absorption spectrum and using 1670cm -1 The absorption peaks at 1635 cm-1 and 1635 cm-2 derived from the ketone groups in the polyimide resin decrease or disappear. -1 This was confirmed by the appearance of an absorption peak derived from an imine group nearby.
[0116] The heating condensation of the ketone group of the DDA-based thermoplastic polyimide in the component (A) and the primary amino group of the crosslink-forming amino compound can be performed, for example, by the following method.
[0117] (1) A method in which an amino compound for crosslinking is added immediately after the synthesis (imidization) of the DDA-based thermoplastic polyimide in the component (A) and heating is performed;
[0118] (2) A method in which an excess amount of an amino compound is added as a diamine component in advance, and then the DDA-based thermoplastic polyimide in the component (A) is synthesized (imidized), and the remaining amino compound that does not participate in imidization or amidation is used as an amino compound for crosslinking and heated together with the DDA-based thermoplastic polyimide;
[0119] or
[0120] (3) A method of heating the composition of the DDA-based thermoplastic polyimide in the component (A) to which the crosslink-forming amino compound is added after processing into a predetermined shape (for example, after coating on an arbitrary substrate or forming into a film).
[0121] In order to impart heat resistance to the DDA-based thermoplastic polyimide in the component (A), the formation of imide bonds is described in the formation of the cross-linked structure, but the present invention is not limited thereto. As a method for curing the polyimide in the component (A), for example, epoxy resin, epoxy resin curing agent, maleimide or activated ester resin or a resin having a styrene skeleton, or other compounds having unsaturated bonds may be formulated for curing.
[0122] [(B) ingredient]
[0123] The resin composition of the present embodiment contains one or more selected from aromatic condensed phosphate esters, silica particles, or liquid crystal polymer fillers as component (B). In addition, two or more components may be used in combination as component (B).
[0124] Hereinafter, the aromatic condensed phosphate ester as "(B1) component", the silica particles as "(B2) component", and the liquid crystalline polymer filler as "(B3) component" will be described in this order.
[0125] [Component (B1); aromatic condensed phosphate ester]
[0126] The so-called "aromatic condensed phosphate" as component (B1) refers to a phosphate compound having a chemical structure in which two or more phosphate units are linked by a divalent organic group having an aromatic ring, or a reaction product of phosphorus oxychloride, a divalent phenolic compound and phenol or an alkylphenol. By combining an aromatic condensed phosphate with a polyimide obtained by using a dimer diamine composition of more than a fixed amount, the dielectric properties can be improved. The reason is not yet clear, but it is speculated that according to the chemical structure peculiar to the aromatic condensed phosphate, although the dielectric properties of the aromatic condensed phosphate itself are compatible with the polyimide obtained by using the dimer diamine composition, it is not excessively improved The mobility of the molecular chain contributes to low dielectric constant and low dielectric loss tangent. In addition, the humidity dependence of the dielectric properties of the resin film obtained using the (B1) component is low, and the stability is excellent.
[0127] Preferred examples of the aromatic condensed phosphate ester include compounds having a structure represented by the following general formula (3).
[0128] [Chemistry 5]
[0129]
[0130] In the general formula (3), a plurality of Rs are independently aromatic hydrocarbon groups which may have a substituent, Ar is a divalent organic group having an aromatic ring, and n is an integer greater than 1. The aromatic condensed phosphate ester represented by the general formula (3) may be a dimer in which n is 1 or a polymer in which n is greater than 2. In addition, it is not limited to a single compound, and a mixture may also be used.
[0131] Examples of the optionally substituted aromatic hydrocarbon group represented by R in the general formula (3) include aryl groups having 6 to 15 carbon atoms, and more specifically, include phenyl, methylphenyl, dimethylphenyl, trimethylphenyl, ethylphenyl, butylphenyl, and nonylphenyl.
[0132] In addition, in the general formula (3), preferred examples of the divalent organic group represented by Ar include alkylene groups and arylene groups, which may have a substituent. More preferred examples of the divalent organic group include phenylene groups and groups represented by the following formula (4).
[0133] [Chemistry 6]
[0134]
[0135] In formula (4), Y1 represents a single bond, -CH2-, -C(CH3)2-, -SO2-, -C5H 10 -、-C6H 12 -、-C7H 14 -、-C8H 16 -wait.
[0136] Among the groups represented by formula (4), a biphenyldiyl group in which Y1 is a single bond is more preferred.
[0137] As the aromatic condensed phosphate ester, for example, resorcinol bis-diphenyl phosphate, resorcinol bis-dixylyl phosphate, bisphenol A bis-diphenyl phosphate, etc. can be cited. As these aromatic condensed phosphate esters, commercial products can be obtained, for example, CR-733S (trade name), CR-741 (trade name), CR-747 (trade name), PX-200 (trade name), PX-200B (trade name) [above, manufactured by Dahachi Chemical Industry Co., Ltd.], etc. These aromatic condensed phosphate esters can be used in combination of two or more.
[0138] <(B1) Component blending amount>
[0139] The weight ratio of the component (B1) in the resin composition of the present embodiment relative to the component (A) is within the range of 0.05 to 0.7. If the film properties such as the tensile elastic coefficient when forming the resin film are considered, it is preferably within the range of 0.2 to 0.5 (the same in the resin film described later). When the weight ratio of the component (B1) relative to the component (A) is less than 0.05, there is a situation where the improvement of the dielectric properties is insufficient. If it exceeds 0.7, there is a situation where it is difficult to form a polyimide, and there is also a situation where the obtained polyimide film is embrittled. By setting the amount of the component (B1) to within the range, the dielectric properties can be improved. Furthermore, the component (A) is set to be converted to polyimide in the case of polyamic acid to calculate the weight ratio (hereinafter, the same).
[0140] In addition, in the resin composition of the present embodiment, the component (B1) is preferably formulated so that the weight ratio of phosphorus derived from the component (B1) relative to the thermoplastic resin of the component (A) is in the range of 0.01 to 0.1. When the weight ratio of phosphorus derived from the component (B1) is less than 0.01, the improvement of dielectric properties is insufficient, and when it exceeds 0.1, there is a case where the polyimide film (or polyimide layer) is embrittled.
[0141] The weight ratio of phosphorus derived from component (B1) in component (B1) of the resin composition of the present embodiment to the dimer diamine composition contained in component (A) {phosphorus derived from component (B1) / dimer diamine composition in component (A)} is preferably in the range of 0.01 to 0.15. If the weight ratio is less than the lower limit, the improvement of dielectric properties may be insufficient, and if the weight ratio is greater than the upper limit, the formation of polyimide may be difficult, and the obtained polyimide film may become brittle.
[0142] [(B2) ingredient: silicon dioxide particles]
[0143] The silica particles as the component (B2) may be either crystalline silica particles or amorphous silica particles, but preferably contain crystalline silica particles having a cristobalite crystal phase or a quartz crystal phase.
[0144] By allocating the silica particles as (B2) component, the dielectric loss tangent when forming the resin film can be reduced. With regard to the viewpoint of realizing the low dielectric loss tangent when forming the resin film, it is particularly preferred to use silica particles with white silica crystal phases as crystalline silica particles. Compared with general silica particles, the dielectric properties of the silica particles with white silica crystal phases are very excellent (for example, the dielectric loss tangent of the silica particles containing more than 90% by weight of white silica crystal phases is about 0.0001 in terms of monomer at 20GHz), which can greatly contribute to the low dielectric loss tangent of the resin film.
[0145] In addition, as the silica particles of the component (B2), spherical silica particles are preferably used. Spherical silica particles are silica particles that are close to spherical in shape and have a ratio of average major axis to average minor axis of 1 or close to 1.
[0146] In addition, since silica does not thermally decompose at a normal combustion temperature, the flame retardancy can be improved by adding silica particles as the component (B2).
[0147] In addition, from the perspective of realizing the low dielectric loss tangent when forming a resin film, as the entire silica particles used, the total area of the peaks of the white silica crystal phase and the quartz crystal phase in the range of 2θ=10°~90° of the X-ray diffraction analysis spectrum of CuKα rays is preferably 20% by weight or more, more preferably 40% by weight or more, and ideally 80% by weight or more. By increasing the proportion of the white silica crystal phase and / or the quartz crystal phase of the entire silica particles, further low dielectric loss tangent of polyimide can be achieved. If the area ratio of the peaks of the white silica crystal phase and the quartz crystal phase in the entire silica particles is less than 20% by weight, the effect of improving the dielectric properties is unclear. Furthermore, in the case where the peak of the object in the X-ray diffraction analysis spectrum is difficult to separate from the amorphous broad peak or overlaps with other crystalline phase peaks, various known analysis methods, such as internal standard method or PONKCS method, can be used.
[0148] The average particle size of silica particles D 50 The average particle size D is preferably in the range of 6 μm to 20 μm, and more preferably in the range of 8 μm to 15 μm. 50 The average particle size D is the value at which the cumulative value in the frequency distribution curve obtained by volume-based particle size distribution measurement using the laser diffraction scattering method becomes 50%. 50 When the average particle size D is within the above range, the dielectric properties can be effectively improved, and a low dielectric film with good appearance can be obtained without deteriorating the surface smoothness when the resin film is formed from the resin composition. 50 If the average particle size D is below the above range, the specific surface area of the silica particles increases, and the adsorbed water or polar groups on the surface of the silica particles may affect the dielectric properties. 50 When the amount exceeds the above range, the unevenness may appear as irregularities on the surface of the resin film, and the smoothness of the film surface may be deteriorated.
[0149] In addition, more than 90% by weight of the silica particles with a particle size of more than 3 μm are preferably circularities of more than 0.7, more preferably more than 0.9. The circularity of the silica particles can be obtained by image analysis, assuming a circle with the same projected area as the particles photographed, and by the ratio of the circumference of the circle to the circumference of the particles. If the circularity is less than 0.7, the surface area increases, which sometimes has an adverse effect on dielectric properties, and then the increase in viscosity when deployed in the resin solution becomes larger and difficult to handle. In addition, it is preferably a value substantially corresponding to the value of the circularity in the sphericity obtained three-dimensionally.
[0150] In addition, the true specific gravity of the silica particles is preferably 2.3 or more. If the true specific gravity is less than 2.3, it is suggested that the crystallinity of the silica particles is small, and the effect of improving the dielectric properties becomes small.
[0151] Silica particles can be selected from commercial products as appropriate. For example, spherical white silica powder (manufactured by Nippon Steel Chemical & Materials Co., Ltd., trade name: CR10-20), spherical amorphous silica powder (manufactured by Nippon Steel Chemical & Materials Co., Ltd., trade name: SC70-2) and the like can be preferably used. Furthermore, two or more different silica particles can also be used as silica particles.
[0152] <(B2) Component blending amount>
[0153] The weight ratio of the component (B2) of the resin composition of the present embodiment to the total of the components (A) and (B2) is within the range of 5% to 60% by weight (the same in the resin film described later). When the weight ratio of the component (B2) to the total of the components (A) and (B2) is less than 5% by weight, the improvement effect of the dielectric properties and flame retardancy is insufficient. If it exceeds 60% by weight, it is difficult to form a polyimide, and the polyimide film obtained is embrittled. By setting the blending amount of the component (B2) to within the range, the dielectric properties and flame retardancy can be improved.
[0154] In addition, when the content of component (B2) is within the range of 5% by weight to 20% by weight relative to the total of component (A) and component (B2), it is preferred to prepare the crystalline silica particles in such a manner that the total area of the peaks derived from the white silica crystal phase and the quartz crystal phase in the range of 2θ=10° to 90° of the X-ray diffraction analysis spectrum using CuKα rays is 40% by weight or more relative to the total area of all peaks derived from SiO2. On the other hand, when the content of component (B2) exceeds 20% by weight relative to the total of component (A) and component (B2), it is preferred to prepare the crystalline silica particles in such a manner that the peak areas derived from the white silica crystal phase and the quartz crystal phase are 30% by weight or more.
[0155] In addition, from the viewpoint of improving the adhesion to a metal layer such as copper foil when forming a resin film, the volume ratio of the component (B2) to the total of the components (A) and (B2) is preferably in the range of 3% to 41%, and more preferably in the range of 10% to 35% (the same in the resin film described later). Furthermore, the volume ratio can be calculated based on the density and weight ratio of the components (A) and (B2) to be formulated, or can be obtained by cross-sectional observation using a scanning electron microscope.
[0156] [(B3) component: liquid crystal polymer filler]
[0157] Liquid crystal polymer fillers are particles containing liquid crystal polymers that form optically anisotropic melt phases. Liquid crystal polymers that form optically anisotropic melt phases are also called thermotropic liquid crystal polymers. The polymers that form optically anisotropic melt phases are polymers that transmit polarized light when a sample in a molten state is observed under crossed Nicols of a polarizing microscope including a heating device. Liquid crystal polymers have almost no frequency dependence, have very excellent dielectric properties, and also contribute to the improvement of flame retardancy. Therefore, by allocating liquid crystal polymers, the dielectric properties and flame retardancy of the resin film can be improved.
[0158] The liquid crystal polymer is not particularly limited, and examples thereof include known thermotropic liquid crystal polyesters and polyester amides derived from compounds classified into the following (1) to (4) and derivatives thereof.
[0159] (1) Aromatic or aliphatic dihydroxy compounds
[0160] (2) Aromatic or aliphatic dicarboxylic acids
[0161] (3) Aromatic hydroxycarboxylic acid
[0162] (4) Aromatic diamines, aromatic hydroxylamines or aromatic aminocarboxylic acids
[0163] The more aromatic rings there are in a liquid crystal polymer, the more effects of improving dielectric properties and flame retardancy can be expected. Therefore, it is preferred to contain an aromatic dihydroxy compound (aromatic diol) as the (1) and an aromatic dicarboxylic acid as the (2).
[0164] A representative example of a liquid crystal polymer obtained from these raw material compounds is a copolymer having a combination of two or more structural units selected from the following formulas (a) to (g), preferably a copolymer containing any one of the structural units represented by formula (a) or (b), and more preferably a copolymer containing the structural unit represented by formula (a) and the structural unit represented by formula (b). Formulas (a) and (b) are representative examples of structural units derived from aromatic hydroxycarboxylic acids, formulas (c), (d), and (e) are representative examples of structural units derived from aromatic dicarboxylic acids, and formulas (f) and (g) are representative examples of structural units derived from aromatic dihydroxy compounds (aromatic diols). Furthermore, in the structural units represented by formulas (a) to (g), the aromatic ring may have an arbitrary substituent.
[0165] In particular, examples of liquid crystal polymers having a low dielectric loss tangent include:
[0166] A liquid crystal polymer comprising structural units represented by formula (a) and formula (b), a structural unit selected from formula (c), formula (d) or formula (e), and a structural unit selected from formula (f) or formula (g) in a specific ratio;
[0167] A liquid crystal polymer comprising a structural unit represented by formula (b), a structural unit selected from formula (c), formula (d) or formula (e), and a structural unit selected from formula (f) or formula (g), etc. at a specific ratio.
[0168] [Chemistry 7]
[0169]
[0170] In order to improve the dielectric properties of the resin film obtained from the resin composition, the following liquid crystalline polymer filler is preferably used: as a monomer, the relative dielectric constant at 10 GHz is preferably in the range of 2.8 to 3.6, more preferably in the range of 3.0 to 3.4, and the dielectric loss tangent at 10 GHz is preferably less than 0.0019, more preferably less than 0.0015.
[0171] In addition, when the dielectric loss tangent of the component (A) at 10 GHz is Dfa and the dielectric loss tangent of the component (B3) at 10 GHz is Dfb, it is more preferable that Dfb is less than 0.0019 and Dfa>Dfb.
[0172] In addition, the liquid crystal polymer preferably contains abundant aromatic rings from the viewpoint of improving flame retardancy. The weight ratio of the aromatic rings in the liquid crystal polymer filler is preferably 60 wt % or more, more preferably 70 wt % or more.
[0173] In addition, it is preferable to use spherical liquid crystal polymer particles as the liquid crystal polymer particles. The spherical liquid crystal polymer particles are liquid crystal polymer particles having a shape close to a sphere and having a ratio of an average major axis to an average minor axis of 1 or close to 1.
[0174] The average particle size D of the liquid crystal polymer particles 50 The average particle size D is preferably in the range of 6 μm to 20 μm, and more preferably in the range of 8 μm to 15 μm. 50 The average particle size D is the value at which the cumulative value in the frequency distribution curve obtained by volume-based particle size distribution measurement using the laser diffraction scattering method becomes 50%. 50 If the average particle size D is within the above range, a low dielectric film with good appearance can be obtained without deteriorating the surface smoothness when a resin film is formed from the resin composition. 50If the average particle size D is less than the above range, the liquid crystal polymer particles may aggregate when preparing the resin composition, and a uniform resin composition may not be obtained. 50 When the amount exceeds the above range, the unevenness may appear as irregularities on the surface of the resin film, and the smoothness of the film surface may be deteriorated.
[0175] The melting point of the liquid crystal polymer is preferably higher than the curing temperature of the resin composition, for example, preferably 250° C. or higher.
[0176] Liquid crystal polymer particles can be appropriately selected and used. For example, low dielectric liquid crystal polymer (manufactured by JXTG Energy Corporation) can be preferably used. Furthermore, two or more different liquid crystal polymer particles can be used in combination as the liquid crystal polymer particles.
[0177] <(B3) Component Amount>
[0178] The ratio of the (B3) component of the resin composition of the present embodiment to the total of the (A) component and the (B3) component is within the range of 15 volume % to 50 volume %, preferably within the range of 15 volume % to 40 volume % (the same in the resin film described later). When the volume ratio of the (B3) component to the total of the (A) component and the (B3) component is less than 15 volume %, there is a situation where the improvement effect of the dielectric properties and flame retardancy is insufficient. If it exceeds 50 volume %, there is a situation where it is difficult to form a polyimide, and there is also a situation where the embrittlement of the obtained resin film is produced. By setting the allocation amount of the (B3) component to the range, the dielectric properties and flame retardancy can be improved. Furthermore, the volume ratio of the (B3) component to the total of the (A) component and the (B3) component can be obtained by observing the cross section of the cured film using a scanning electron microscope, etc., and calculating the ratio of the liquid crystal polymer filler in the resin composition.
[0179] [Optional Ingredients]
[0180] The resin composition of the present embodiment may contain an organic solvent. For example, it may be a polyimide solution containing a solvent-soluble DDA-based thermoplastic polyimide and a solvent. As an organic solvent, for example, N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), N,N-diethylacetamide, N-methyl-2-pyrrolidone (NMP), 2-butanone, dimethyl sulfoxide (DMSO), hexamethylphosphoramide, N-methylcaprolactam, dimethyl sulfate, cyclohexanone, dioxane, tetrahydrofuran, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, cresol, etc. It is also possible to use two or more of these solvents, and further, it is also possible to use aromatic hydrocarbons such as xylene and toluene. As the content of the organic solvent, there is no particular limitation, and it is preferably used in an amount such that the concentration of the thermoplastic resin is adjusted to be about 5% by weight to 30% by weight.
[0181] In addition, the resin composition of the present embodiment may contain a flame retardant when using a liquid crystal polymer filler as the (B) component. As a flame retardant, there is no particular limitation, but it is preferably a phosphorus flame retardant. Aliphatic thermoplastic resins such as DDA thermoplastic polyimide have low aromatic ring concentrations, so even if a phosphorus flame retardant is added, the flame retardant properties cannot be fully exerted, but in the resin composition with a liquid crystal polymer filler of the (B3) component, the concentration becomes high due to the aromatic rings derived from the liquid crystal polymer, so the formation of carbon (carbonized film) during combustion is promoted, and a high flame retardant effect is exerted. From the above point of view, when using a liquid crystal polymer filler as the (B3) component, relative to 100% by weight of the non-volatile organic compound component of the resin composition, it is preferably further added with 15% to 30% by weight of a phosphorus flame retardant. Here, the so-called "non-volatile organic compound component" refers to the remaining solid component after removing the solvent and the inorganic solid component from the resin composition. That is, the non-volatile organic compound component contains a thermoplastic resin as component (A) and a liquid crystal polymer filler as component (B3), and as an optional component, may contain a resin other than the thermoplastic resin, an organic filler other than the liquid crystal polymer filler, a plasticizer, a hardening accelerator, a coupling agent, an organic pigment, an organic flame retardant other than the phosphorus flame retardant, etc.
[0182] Phosphorus-based flame retardants include, for example, aromatic condensed phosphates having the same structure as the component (B1), metal salts of organic phosphinic acids, alkyl phosphines (excluding red phosphorus), etc. These flame retardants may be used in combination of two or more different compounds.
[0183] The metal salt of an organic phosphinic acid is, for example, a metal salt of phosphoric acid in which two organic groups are bonded to phosphorus, as represented by the following general formula (5).
[0184] [Chemistry 8]
[0185]
[0186] In the general formula (5), the two organic groups R 11 and R 12 Preferably, they are identical or different straight-chain or branched alkyl groups with 1 to 6 carbon atoms, phenyl groups, or tolyl groups. In addition, in the general formula (5), the metal type M is preferably selected from the group consisting of Mg, Ca, Al, Sb, Sn, Ge, Ti, Fe, Zr, Ce, Bi, Sr, Mn, Li, Na, and K. Furthermore, when the metal type M is an n-valent metal with a valence of two or more, M in the general formula (5) is transformed into M1 / n. In addition, in order to improve the flame retardant effect, it is preferred to increase the phosphorus content. Specifically, the two organic groups R 11 and R 12An alkyl group having 1 to 3 carbon atoms is preferred. In order to improve flame retardancy and flexibility and suppress solubility in water as a metal salt, the metal species M is preferably aluminum (Al).
[0187] As the metal salt of the organic phosphinic acid, commercially available products are available, and examples thereof include aluminum phosphinic acid salts manufactured by Clariant Japan Co., Ltd., namely Exolit OP930 (trade name), Exolit OP935 (trade name), and Exolit OP940 (trade name).
[0188] In the resin composition of the present embodiment, other resin components other than the thermoplastic resin of component (A), inorganic fillers other than crosslinking agents, silica particles, organic fillers other than liquid crystal polymer fillers, plasticizers, hardening accelerators, coupling agents, pigments, etc. can be appropriately prepared as required as arbitrary components. As crosslinking agents, amino compounds (crosslinking forming amino compounds), epoxy compounds, bismaleimide compounds, acrylic acid (methacrylic acid) compounds, etc. having at least two primary amino groups as functional groups can be listed. As inorganic fillers, for example, aluminum oxide, magnesium oxide, beryllium oxide, boron nitride, aluminum nitride, silicon nitride, aluminum fluoride, calcium fluoride, etc. can be listed. These can be used one or mixed with two or more.
[0189] [Viscosity]
[0190] As a viscosity range for improving the handling property when applying the resin composition and facilitating the formation of a coating film of uniform thickness, the viscosity of the resin composition is preferably set in the range of 3000 cps to 100000 cps, and more preferably in the range of 5000 cps to 50000 cps. If the viscosity deviates from the above range, it is easy to cause defects such as uneven thickness and streaks in the film when applying the film using a coater or the like.
[0191] [Preparation of resin composition]
[0192] The resin composition of the present embodiment can be prepared by, for example, preparing a solution of the component (A) using an arbitrary solvent, adding the component (B) thereto, and uniformly mixing the solution.
[0193] For example, the component (B) may be directly mixed with the resin solution of the DDA-based thermoplastic polyimide. Furthermore, a part of the component (A) may be mixed simultaneously with the component (B) or after the component (B) is added.
[0194] In any method, the component (B) may be added all at once or added little by little in several times. In addition, the raw materials may be added all at once or mixed little by little in several times.
[0195] The resin composition of the present embodiment, when used to form an adhesive layer, has excellent flexibility and thermoplasticity, as well as excellent dielectric properties and flame retardancy. Therefore, the resin composition of the present embodiment has preferred properties as a cover film adhesive for protecting wiring parts such as FPC, rigid / flexible circuit substrates.
[0196] [Resin film]
[0197] The resin film of the present embodiment is a resin film comprising a thermoplastic resin layer (preferably a DDA-based thermoplastic polyimide layer), wherein the thermoplastic resin layer is formed by filming the solid component of the resin composition (the remaining portion after removing the solvent) as the main component. That is, the resin film of the present embodiment contains component (A) and component (B), and the weight ratio of component (B) to component (A) is adjusted to be within a specified range in the same manner as the resin composition. In addition to flexibility and adhesion, the resin film of the present embodiment also has excellent high-frequency characteristics and flame retardancy, and therefore can be preferably used for applications such as protecting the adhesive layer for the cover film of the wiring part such as FPC, rigid / flexible circuit substrates, or the bonding sheet of a multilayer FPC.
[0198] The resin film of this embodiment is not particularly limited as long as it is a film of an insulating resin including a thermoplastic resin layer formed from the resin composition. It may be a film (sheet) including an insulating resin, or a film of an insulating resin in a state of being laminated on a substrate such as a resin sheet such as a copper foil, a glass plate, a polyimide film, a polyamide film, or a polyester film.
[0199] <Glass transition temperature>
[0200] The glass transition temperature (Tg) of the resin film of this embodiment is preferably 250°C or less, and more preferably in the range of 40°C or more and 200°C or less. When the Tg of the resin film is 250°C or less, thermocompression bonding can be performed at low temperatures, thereby relaxing the internal stress generated during lamination and suppressing dimensional changes after circuit processing. If the Tg of the resin film exceeds 250°C, the temperature will then increase, and there is a risk of damaging the dimensional stability after circuit processing.
[0201] When the component (B1) is used as the component (B), the resin film preferably has the following physical properties.
[0202] <Dielectric properties>
[0203] When the component (B1) is used as the component (B), the resin film is based on the following formula (i):
[0204] E1=√ε1×Tanδ1···(i)
[0205] [Here, ε1 represents the relative dielectric constant at 10 GHz measured by a separation dielectric resonator (SPDR) after humidification for 24 hours under constant temperature and humidity conditions (normal state) of 23°C and 50%RH, and Tanδ1 represents the dielectric loss tangent at 10 GHz measured by SPDR after humidification for 24 hours under constant temperature and humidity conditions of 23°C and 50%RH. Furthermore, "√ε1" refers to the square root of ε1] and the E1 value, which is an index of dielectric properties at 10 GHz after humidification for 24 hours under constant temperature and humidity conditions of 23°C and 50%RH, is calculated to be less than 0.010, preferably less than 0.009, and more preferably less than 0.008. If the E1 value exceeds the upper limit, when used in a circuit substrate such as an FPC, it is easy to cause undesirable conditions such as loss of electrical signals on the transmission path of high-frequency signals.
[0206] <Relative dielectric constant>
[0207] When the component (B1) is used as the component (B), the relative dielectric constant (ε1) at 10 GHz after humidity adjustment for 24 hours at a constant temperature and humidity of 23°C and 50%RH is preferably 3.2 or less, more preferably 3.0 or less, in order to ensure impedance matching when used in a circuit substrate such as an FPC and to reduce the loss of electrical signals. If the relative dielectric constant exceeds 3.2, when used in a circuit substrate such as an FPC, it is easy to cause disadvantages such as loss of electrical signals on the transmission path of high-frequency signals.
[0208] <Dielectric loss tangent>
[0209] In addition, when the component (B1) is used as the component (B), in order to reduce the loss of electrical signals when used in a circuit substrate such as an FPC, the dielectric loss tangent (Tanδ1) at 10 GHz after humidity adjustment for 24 hours under constant temperature and humidity conditions of 23°C and 50%RH is preferably less than 0.005, and more preferably less than 0.004. If the dielectric loss tangent is 0.005 or more, when used in a circuit substrate such as an FPC, it is easy to cause disadvantages such as loss of electrical signals on the transmission path of high-frequency signals.
[0210] <Moisture absorption dependence>
[0211] When the component (B1) is used as the component (B), in order to reduce the loss of electrical signals in dry and wet conditions or to ensure impedance matching when the resin film is used in a circuit board such as an FPC, the following formula (ii) is used:
[0212] E2=√ε2×Tanδ2···(ii)
[0213] [Here, ε2 represents the relative dielectric constant at 10 GHz measured by SPDR after absorbing water at 23°C for 24 hours, and Tanδ2 represents the dielectric loss tangent at 10 GHz measured by SPDR after absorbing water at 23°C for 24 hours. In addition, "√ε2" means the square root of ε2]
[0214] The calculated E2 value, which is an index of dielectric properties at 10 GHz after absorbing water for 24 hours at 23°C, has a ratio (E2 / E1) of the E2 value to the E1 value calculated based on the formula (i) in the range of 3.0 to 1.0, preferably in the range of 2.5 to 1.0, and more preferably in the range of 2.2 to 1.0. If E2 / E1 exceeds the upper limit, when used in a circuit substrate such as an FPC, for example, the relative dielectric constant and dielectric loss tangent increase when wet, and it is easy to cause disadvantages such as loss of electrical signals in the transmission path of high-frequency signals.
[0215] <Moisture absorption rate>
[0216] When using (B1) component as (B) component, about resin film, in order to reduce the influence caused by humidity when used in circuit substrates such as FPC, the moisture absorption rate of resin film is preferably preferably less than 0.5 weight %, more preferably less than 0.3 weight %. Here, "hygroscopicity" refers to the moisture absorption rate (same meaning in this specification) after more than 24 hours under constant temperature and humidity conditions of 23 ° C and 50% RH. If the moisture absorption rate of resin film exceeds 0.5 weight %, it is easily affected by humidity when used in circuit substrates such as FPC, and it is easy to produce undesirable conditions such as changes in the transmission speed of high-frequency signals. That is, if the moisture absorption rate of resin film exceeds the range, it is easy to absorb water with high relative dielectric constant, thus causing the rise of relative dielectric constant and dielectric loss tangent, and it is easy to produce undesirable conditions such as loss of electrical signals on the transmission path of high-frequency signals.
[0217] <Storage elastic coefficient>
[0218] When component (B1) is used as component (B), the resin film may be a resin film having a temperature range in the range of 40°C to 250°C in which the storage elastic coefficient decreases at a steep rate as the temperature rises. Such a property of the resin film is believed to be a factor in relaxing internal stress during, for example, thermal compression bonding and maintaining dimensional stability after circuit processing. The storage elastic coefficient of the resin film at the upper limit temperature of the temperature range is preferably 5×10 7[Pa] or less. By setting such a storage elastic coefficient, even if it is set to the upper limit of the temperature range, hot pressing can be performed at 250°C or less, which can ensure adhesion and suppress dimensional changes after circuit processing. Furthermore, although the resin film of this embodiment has high thermal expansion, it has low elasticity, so even if the thermal expansion coefficient (CTE) exceeds 30ppm / K, the internal stress generated during lamination can be relaxed.
[0219] When the component (B2) is used as the component (B), the resin film preferably has the following physical properties.
[0220] <Relative dielectric constant>
[0221] When the component (B2) is used as the component (B), the relative dielectric constant at 20 GHz after humidity adjustment for 24 hours at a constant temperature and humidity of 23°C and 50%RH is preferably 3.2 or less, more preferably 3.0 or less, in order to ensure impedance matching when used in a circuit substrate such as an FPC and to reduce the loss of electrical signals. If the relative dielectric constant exceeds 3.2, when used in a circuit substrate such as an FPC, it is easy to cause disadvantages such as loss of electrical signals on the transmission path of high-frequency signals.
[0222] <Dielectric loss tangent>
[0223] In addition, when the component (B2) is used as the component (B), in order to reduce the loss of electrical signals when used in a circuit substrate such as an FPC, the dielectric loss tangent at 20 GHz after humidity adjustment for 24 hours under constant temperature and humidity conditions of 23°C and 50% RH is preferably less than 0.005, more preferably less than 0.004, and most preferably less than 0.002. If the dielectric loss tangent is greater than 0.005, when used in a circuit substrate such as an FPC, it is easy to cause an undesirable situation such as loss of electrical signals on the transmission path of high-frequency signals.
[0224] When the component (B3) is used as the component (B), the resin film preferably has the following physical properties.
[0225] <Relative dielectric constant>
[0226] When the component (B3) is used as the component (B), the relative dielectric constant at 20 GHz after humidity adjustment for 24 hours at a constant temperature and humidity of 23°C and 50%RH is preferably 3.2 or less, more preferably 3.0 or less, in order to ensure impedance matching when used in a circuit substrate such as an FPC and to reduce the loss of electrical signals. If the relative dielectric constant exceeds 3.2, when used in a circuit substrate such as an FPC, it is easy to cause disadvantages such as loss of electrical signals on the transmission path of high-frequency signals.
[0227] <Dielectric loss tangent>
[0228] In addition, when the component (B3) is used as the component (B), in order to reduce the loss of electrical signals when used in a circuit substrate such as an FPC, the dielectric loss tangent at 20 GHz after humidity adjustment for 24 hours under constant temperature and humidity conditions of 23°C and 50% RH is preferably less than 0.005, more preferably less than 0.004, and most preferably less than 0.002. If the dielectric loss tangent is greater than 0.005, when used in a circuit substrate such as an FPC, it is easy to cause an undesirable situation such as loss of electrical signals on the transmission path of high-frequency signals.
[0229] <Thickness>
[0230] When the component (B1) is used as the component (B), the thickness of the resin film is preferably within a range of 5 μm to 125 μm, and more preferably within a range of 8 μm to 100 μm. If the thickness of the resin film is less than 5 μm, there is a risk of wrinkles and other undesirable conditions occurring during the transportation of the resin film during the manufacture of the resin film, while on the other hand, if the thickness of the resin film exceeds 125 μm, there is a risk of reduced productivity of the resin film.
[0231] In addition, when the component (B2) or the component (B3) is used as the component (B), the thickness of the resin film is preferably in the range of 15 μm to 100 μm, and more preferably in the range of 20 μm to 50 μm. If the thickness of the resin film is less than 15 μm, there is a risk of wrinkles and other undesirable conditions occurring during the transportation of the resin film during the manufacture of the resin film, while on the other hand, if the thickness of the resin film exceeds 100 μm, there is a risk of reduced productivity of the resin film.
[0232] When the thickness of the resin film is within the range of 15 μm to 20 μm, in order to suppress the unevenness of the resin film surface and maintain the smoothness of the film surface, the silica particles as the component (B2) or the liquid crystal polymer filler as the component (B3) preferably have an average particle size D 50 Those within the range of 9 μm to 12 μm.
[0233] [Laminated body]
[0234] The laminate of one embodiment of the present invention comprises a substrate and an adhesive layer laminated on at least one surface of the substrate, wherein the adhesive layer comprises the resin film. Furthermore, the laminate may comprise any layer other than the above. As the substrate in the laminate, for example, a substrate of an inorganic material such as copper foil and a glass plate, or a substrate of a resin material such as a polyimide film, a polyamide film, and a polyester film can be cited.
[0235] Preferred forms of the laminate include a coverlay film and a copper foil with a resin.
[0236] [Cover film]
[0237] A cover film as one form of a laminate includes a cover film material layer as a base material and an adhesive layer laminated on one side of the cover film material layer, wherein the adhesive layer includes the resin film. The cover film may include any layer other than the above.
[0238] The material of the covering film material layer is not particularly limited, and for example, polyimide films such as polyimide, polyetherimide, polyamide-imide, or polyamide films, polyester films, etc. can be used. Among these, it is preferred to use a polyimide film with excellent heat resistance. In addition, in order to effectively show light-shielding properties, concealment, design, etc., the covering film material may also contain a black pigment, and in addition, any component such as a matte pigment that suppresses the surface gloss may be included within the range that does not damage the improvement effect of the dielectric properties.
[0239] The thickness of the covering film material layer is not particularly limited, but is preferably within a range of 5 μm to 100 μm, for example.
[0240] The thickness of the adhesive layer is not particularly limited, but is preferably within a range of 10 μm to 75 μm, for example.
[0241] The cover film of the present embodiment can be produced by the method exemplified below.
[0242] First, as a first method, a varnish-like resin composition containing a solvent is applied to one surface of a covering film material layer and then dried at, for example, 80° C. to 180° C. to form an adhesive layer, thereby forming a covering film having a covering film material layer and an adhesive layer.
[0243] In addition, as a second method, a varnish-like resin composition containing a solvent is coated on an arbitrary substrate, and then dried at a temperature of, for example, 80°C to 180°C and then peeled off to form an adhesive film for an adhesive layer. The adhesive film and a covering film material layer are heat-pressed together at a temperature of, for example, 60°C to 220°C to form a covering film.
[0244] [Copper foil with resin]
[0245] The copper foil with resin as another embodiment of the laminate is formed by laminating an adhesive layer on at least one side of the copper foil as a base material, and the adhesive layer includes the above-mentioned resin film. In addition, the copper foil with resin of this embodiment may include any layer other than the above-mentioned layers.
[0246] The thickness of the adhesive layer in the copper foil with resin is preferably in the range of 2 μm to 125 μm, more preferably in the range of 2 μm to 100 μm. If the thickness of the adhesive layer is less than the lower limit, problems such as insufficient adhesion may occur. On the other hand, if the thickness of the adhesive layer exceeds the upper limit, undesirable conditions such as reduced dimensional stability may occur. In addition, from the perspective of low dielectric constant and low dielectric loss tangent, it is preferred that the thickness of the adhesive layer be set to 3 μm or more.
[0247] The material of the copper foil in the copper foil with resin is preferably a copper foil with copper or copper alloy as the main component. The thickness of the copper foil is preferably 35 μm or less, and more preferably in the range of 5 μm to 25 μm. From the viewpoint of production stability and handling properties, the lower limit of the thickness of the copper foil is preferably set to 5 μm. Furthermore, the copper foil may be a rolled copper foil or an electrolytic copper foil. In addition, as the copper foil, a commercially available copper foil can be used.
[0248] The copper foil with resin can be prepared, for example, by sputtering a metal on a resin film to form a seed layer, and then forming a copper layer by copper plating, or by laminating a resin film and a copper foil by a method such as thermocompression bonding. Furthermore, the copper foil with resin can be prepared by casting a coating liquid of a resin composition, drying to form a coating film, and then performing a desired heat treatment to form an adhesive layer on the copper foil.
[0249] [Metal-clad laminate]
[0250] (First Form)
[0251] A metal-clad laminate according to an embodiment of the present invention comprises an insulating resin layer and a metal layer laminated on at least one surface of the insulating resin layer, wherein at least one insulating resin layer comprises the resin film. The metal-clad laminate according to this embodiment may comprise any layer other than the above.
[0252] (Second Form)
[0253] Another embodiment of the metal-clad laminate of the present invention is, for example, a so-called three-layer metal-clad laminate including an insulating resin layer, an adhesive layer laminated on at least one side of the insulating resin layer, and a metal layer laminated on the insulating resin layer through the adhesive layer, and the adhesive layer includes the resin film. Furthermore, the three-layer metal-clad laminate may include any layer other than the above. The adhesive layer of the three-layer metal-clad laminate only needs to be arranged on one side or both sides of the insulating resin layer, and the metal layer only needs to be arranged on one side or both sides of the insulating resin layer through the adhesive layer. That is, the three-layer metal-clad laminate may be a single-sided metal-clad laminate or a double-sided metal-clad laminate. A single-sided FPC or a double-sided FPC can be manufactured by etching the metal layer of the three-layer metal-clad laminate and performing wiring circuit processing.
[0254] The insulating resin layer in the three-layer metal-clad laminate is not particularly limited as long as it includes a resin having electrical insulation properties, and examples thereof include polyimide, epoxy resin, phenolic resin, polyethylene, polypropylene, polytetrafluoroethylene, silicone, ETFE, etc., preferably polyimide. The polyimide layer constituting the insulating resin layer may be a single layer or a multilayer, and preferably includes a non-thermoplastic polyimide layer.
[0255] The thickness of the insulating resin layer in the three-layer metal-clad laminate is preferably in the range of 1 μm to 125 μm, and more preferably in the range of 5 μm to 100 μm. If the thickness of the insulating resin layer is less than the lower limit, problems such as failure to ensure sufficient electrical insulation may occur. On the other hand, if the thickness of the insulating resin layer exceeds the upper limit, the three-layer metal-clad laminate may be prone to warping.
[0256] The thickness of the adhesive layer in the three-layer metal-clad laminate is preferably in the range of 0.1μm to 125μm, and more preferably in the range of 0.3μm to 100μm. In the three-layer metal-clad laminate of the present embodiment, if the thickness of the adhesive layer is less than the lower limit, problems such as insufficient adhesion may sometimes occur. On the other hand, if the thickness of the adhesive layer exceeds the upper limit, undesirable conditions such as reduced dimensional stability may occur. In addition, from the perspective of low dielectric constant and low dielectric loss tangent of the entire insulating layer of the laminate of the insulating resin layer and the adhesive layer, the thickness of the adhesive layer is preferably set to 3μm or more.
[0257] In addition, the ratio of the thickness of the insulating resin layer to the thickness of the adhesive layer (the thickness of the insulating resin layer / the thickness of the adhesive layer) is preferably in the range of 0.1 to 3.0, and more preferably in the range of 0.15 to 2.0. By setting such a ratio, the warping of the three-layer metal-clad laminate can be suppressed. In addition, the insulating resin layer may contain a filler as needed. As fillers, for example, silicon dioxide, aluminum oxide, magnesium oxide, beryllium oxide, boron nitride, aluminum nitride, silicon nitride, aluminum fluoride, calcium fluoride, metal salts of organic phosphinates, etc. These can be used alone or in a mixture of two or more.
[0258] [Circuit board]
[0259] The circuit substrate of one embodiment of the present invention is obtained by wiring the metal layer of the metal-clad laminate of any of the above-mentioned embodiments. One or more metal layers of the metal-clad laminate are processed into a pattern by conventional methods to form a wiring layer (conductor circuit layer), thereby manufacturing a circuit substrate such as an FPC. Furthermore, the circuit substrate may also include a cover film covering the wiring layer.
[0260] Example
[0261] The following examples are shown to more specifically describe the features of the present invention. However, the scope of the present invention is not limited to the examples. In the following examples, unless otherwise specified, various measurements and evaluations are performed using the following.
[0262] [Determination method of amine value]
[0263] Weigh about 2 g of the dimer diamine composition into a 200 mL to 250 mL Erlenmeyer flask, use phenolphthalein as an indicator, add 0.1 mol / L ethanolic potassium hydroxide solution until the solution turns light pink, and dissolve it in about 100 mL of neutralized butanol. Add 3 to 7 drops of phenolphthalein solution, and titrate with 0.1 mol / L ethanolic potassium hydroxide solution while stirring until the sample solution turns light pink. Add 5 drops of bromophenol blue solution, and titrate with 0.2 mol / L hydrochloric acid / isopropanol solution while stirring until the sample solution turns yellow.
[0264] The amine value is calculated using the following formula (1).
[0265] Amine value = {(V2×C2)-(V1×C1)}×M KOH / m…(1)
[0266] Here, the amine value is a value expressed by mgKOH / g, M KOHThe molecular weight of potassium hydroxide is 56.1. In addition, V and C are the volume and concentration of the solution used in the titration, respectively, and the subscripts 1 and 2 represent 0.1 mol / L ethanolic potassium hydroxide solution and 0.2 mol / L hydrochloric acid / isopropanol solution, respectively. Furthermore, m is the sample weight expressed in grams.
[0267] [Measurement of Weight Average Molecular Weight (Mw) of Polyimide]
[0268] The weight average molecular weight was measured by gel permeation chromatography (manufactured by TOSOH Co., Ltd., using HLC-8220GPC). Polystyrene was used as a standard substance, and tetrahydrofuran (THF) was used as a developing solvent.
[0269] [GPC and calculation of area percentage of chromatogram]
[0270] Regarding GPC, 100 mg of a solution obtained by pre-treating 20 mg of a dimer diamine composition with 200 μL of acetic anhydride, 200 μL of pyridine and 2 mL of THF was diluted with 10 mL of THF (containing 1000 ppm of cyclohexanone) to prepare a sample. The prepared sample was measured using a product name: HLC-8220GPC manufactured by Tosoh Corporation, under the conditions of column: TSK-gel G2000HXL, G1000HXL, flow rate: 1 mL / min, column (oven) temperature: 40°C, injection volume: 50 μL. In addition, cyclohexanone was treated as a standard substance in order to correct the elution time.
[0271] At this time, the peak top of the main peak of cyclohexanone was adjusted to a retention time of 27 minutes to 31 minutes, and the peak-to-peak time of the main peak of cyclohexanone was adjusted to 2 minutes, and the peak top of the main peak excluding the peak of cyclohexanone was adjusted to a retention time of 18 minutes to 19 minutes, and the peak-to-peak time of the main peak excluding the peak of cyclohexanone was adjusted to a retention time of 4 minutes and 30 seconds from 2 minutes, and the components (a) to (c) were detected;
[0272] (a) The component represented by the main peak;
[0273] (b) The component represented by the GPC peak detected at a later time than the minimum value on the later retention time side of the main peak;
[0274] (c) The component represented by the GPC peak detected at an earlier time than the minimum value on the earlier retention time side of the main peak.
[0275] [Evaluation of Dielectric Properties]
[0276] Using a vector network analyzer (manufactured by Agilent, trade name: Vector Network Analyzer E8363C) and an SPDR resonator, the polyimide film (cured polyimide film) was left at a temperature of 23° C. and a humidity of 50% for 24 hours, and the relative dielectric constant (ε1) and dielectric loss tangent (Tanδ1) at a frequency of 10 GHz were measured. In addition, after absorbing water at 23° C. for 24 hours, the relative dielectric constant (ε2) and dielectric loss tangent (Tanδ2) of the polyimide film (cured polyimide film) at a frequency of 10 GHz were measured.
[0277] [Determination of moisture absorption]
[0278] Two polyimide film test pieces (4 cm wide x 25 cm long) were prepared and dried at 80°C for 1 hour. Immediately after drying, they were placed in a constant temperature and humidity chamber at 23°C / 50%RH for more than 24 hours, and the weight change before and after was determined using the following formula.
[0279] Moisture absorption rate (weight %) = [(weight after moisture absorption - weight after drying) / weight after drying] × 100
[0280] [Determination of water absorption]
[0281] Two polyimide film test pieces (4 cm in width x 25 cm in length) were prepared and dried at 80°C for 1 hour. Immediately after drying, they were placed in pure water at 23°C and left to stand for 24 hours or more, and the weight change before and after was calculated using the following formula.
[0282] Water absorption (weight %) = [(weight after water absorption - weight after drying) / weight after drying] × 100
[0283] [Glass transition temperature (Tg) and storage elastic coefficient]
[0284] The glass transition temperature (Tg) and storage elastic modulus were measured on a polyimide film of 5 mm × 20 mm size using a dynamic viscoelasticity measuring device (DMA: manufactured by DBM, trade name: E4000F) from 30°C to 400°C at a heating rate of 4°C / min and a frequency of 11 Hz. The temperature at which the elastic modulus change (tan δ) was the largest was defined as the glass transition temperature.
[0285] [Tensile elastic coefficient]
[0286] The tensile modulus of elasticity was determined by performing a tensile test at 25° C. using a test piece of 12.7 mm in width and 127 mm in length at 50 mm / min using a tension tester (manufactured by Orientec, trade name Tensilon).
[0287] [Solder heat resistance test (dry)]
[0288] Prepare the following printed substrate: Process the circuit of a polyimide copper-clad laminate (manufactured by Nippon Steel Chemical & Materials Co., Ltd., trade name: Espanex MB12-25-12UEG) to form a circuit with a wiring width / wiring spacing (L / S) = 1 mm / 1 mm. Place the adhesive surface of the test piece on the wiring of the printed substrate and press it under the conditions of a temperature of 160°C, a pressure of 3.5 MPa, and a time of 60 minutes. After drying the test piece with copper foil at 105°C, immerse it in a solder bath set to each evaluation temperature for 10 seconds, observe its bonding state, and confirm whether there are any adverse conditions such as foaming, expansion, and peeling. Heat resistance is expressed by the upper limit temperature at which no adverse conditions occur. For example, "320°C" means that the evaluation is performed in a solder bath at 320°C, and no adverse conditions are confirmed.
[0289] [Solder heat resistance test (moisture absorption)]
[0290] Prepare the following printed substrate: a polyimide copper-clad laminate (manufactured by Nippon Steel Chemical & Materials Co., Ltd., trade name: Espanex MB12-25-12UEG) is processed for circuits to form a circuit with wiring width / wiring spacing (L / S) = 1 mm / 1 mm. The adhesive surface of the test piece is placed on the wiring of the printed substrate and pressed under the conditions of a temperature of 160°C, a pressure of 3.5 MPa, and a time of 60 minutes. After the test piece with copper foil is placed at 40°C and a relative humidity of 80% for 72 hours, it is immersed in a solder bath set to each evaluation temperature for 10 seconds, and its bonding state is observed to confirm whether there are any adverse conditions such as foaming, expansion, and peeling. Heat resistance is expressed by the upper limit temperature at which no adverse conditions occur. For example, "260°C" means that no adverse conditions are confirmed when the evaluation is performed in a solder bath at 260°C.
[0291] [Determination of peel strength]
[0292] The peel strength was measured using a Strograph VE-10 tester (manufactured by Toyo Seiki Seisaku-sho, Ltd.). The resin layer side of a 1 mm wide sample (comprising a laminate of substrate / resin layer) was fixed to an aluminum plate using double-sided tape, and the force applied when the resin layer and the substrate were peeled off at a speed of 50 mm / min in a 180° direction with respect to the substrate was determined.
[0293] [Evaluation of warping]
[0294] The polyimide solution was applied to a polyimide film material with a thickness of 25 μm (manufactured by DuPont Toray, trade name: Kapton 100EN) or a copper foil with a thickness of 12 μm in such a manner that the thickness after drying was 25 μm, thereby preparing a test piece. In the above state, the test piece was placed in such a manner that the polyimide film material or the copper foil became the lower surface, and the average height of the warping of the four corners of the test piece was measured, and the case of less than 5 mm was set as "good", and the case of more than 5 mm was set as "unacceptable".
[0295] The abbreviations used in the present examples represent the following compounds.
[0296] DDA1: PRIAMINE 1075 (trade name) manufactured by Croda Japan Co., Ltd., purified by distillation (component a: 98.2 wt%, component b: 0%, component c: 1.9%, amine value: 206 mgKOH / g)
[0297] DDA2: A product obtained by distilling and refining PRIAMINE 1075 (trade name: Croda Japan Co., Ltd.) (component a: 99.2 wt%, component b: 0%, component c: 0.8%, amine value: 210 mgKOH / g)
[0298] APB: 1,3-bis(3-aminophenoxy)benzene
[0299] BTDA: 3,3',4,4'-Benzophenonetetracarboxylic dianhydride
[0300] N-12: Dodecanedioic acid dihydrazide
[0301] NMP: N-methyl-2-pyrrolidone
[0302] PX-200: Phosphate ester (manufactured by Daba Chemical Industry Co., Ltd., trade name: PX-200, non-halogen aromatic condensed phosphate ester, phosphorus content: 9.0%)
[0303] PX-202: Phosphate ester (manufactured by Daba Chemical Industry Co., Ltd., trade name: PX-202, non-halogen aromatic condensed phosphate ester, phosphorus content: 8.1%)
[0304] SR-3000: Phosphate ester (manufactured by Daba Chemical Industry Co., Ltd., trade name: SR-3000, non-halogen aromatic condensed phosphate ester, phosphorus content: 7.0%)
[0305] DA-850: Phosphate ester (manufactured by Dahachi Chemical Industry Co., Ltd., trade name: DAIGUARD-850, non-halogen aromatic condensed phosphate ester, phosphorus content: 16.0% or more)
[0306] TPP (manufactured by Dahachi Chemical Industry Co., Ltd., trade name: TPP, non-halogen phosphate, phosphorus content: 9.5%)
[0307] TCP (manufactured by Dahachi Chemical Industry Co., Ltd., trade name: TCP, non-halogen phosphate, phosphorus content: 8.4%)
[0308] TXP (manufactured by Daba Chemical Industry Co., Ltd., trade name: TXP, non-halogen phosphate, phosphorus content: 7.6%)
[0309] CR-733 (manufactured by Dahachi Chemical Industry Co., Ltd., trade name: CR-733S, non-halogen aromatic condensed phosphate, phosphorus content: 10.9%)
[0310] CR-741 (manufactured by Dahachi Chemical Industry Co., Ltd., trade name: CR-741, non-halogen aromatic condensed phosphate, phosphorus content: 8.9%)
[0311] CM-6R: phosphorus-nitrogen compound (manufactured by Yamato Chemical Industry Co., Ltd., trade name: Fran CM-6R, average particle size 5 μm)
[0312] MC-6000: (manufactured by Nissan Chemical Co., Ltd., trade name: MC-6000, non-halogen melamine isocyanurate)
[0313] Filler 1: manufactured by Nippon Steel Chemical & Materials Co., Ltd., trade name: CR10-20 (spherical white silica silicon dioxide powder, spherical, silicon dioxide content: 99.4% by weight, white silica crystal phase: 93% by weight, true specific gravity: 2.33, D 50 :10.8μm,D 90 :16.4μm,D 100 : 24.1μm, relative dielectric constant at 10GHz: 3.16, dielectric loss tangent at 10GHz: 0.0008)
[0314] Filler 2: manufactured by Nippon Steel Chemical & Materials Co., Ltd., trade name: SC70-2 (spherical amorphous silica powder, spherical shape, silica content: 99.9% by weight, true specific gravity: 2.21, D 50 :11.7μm,D 90 :16.4μm,D 100: 24.1μm, relative dielectric constant at 10GHz: 3.08, dielectric loss tangent at 10GHz: 0.0015)
[0315] Flame retardant 1: manufactured by Clariant Japan, trade name: Exolit OP935 (alkyl aluminum phosphate)
[0316] Flame retardant 2: manufactured by Daihachi Chemical Co., Ltd., trade name: SR-3000 (condensed phosphate ester)
[0317] LCP filler: manufactured by JXTG Energy Corporation (low dielectric liquid crystal polymer, particle size (D 50 ): 9.6μm, relative dielectric constant at 10GHz: 3.27, dielectric loss tangent at 10GHz: 0.0009)
[0318] In the above-mentioned DDA1 and DDA2, "%" of component b and component c refers to the area percentage of the chromatogram in the GPC measurement. The molecular weights of DDA1 and DDA2 were calculated by the following formula (1).
[0319] Molecular weight = 56.1 × 2 × 1000 / amine value···(1)
[0320] (Synthesis Example 1-1)
[0321] 55.51 g of BTDA (0.1721 mol), 94.49 g of DDA1 (0.1735 mol), 210 g of NMP and 140 g of xylene were placed in a 1000 ml separable flask and mixed thoroughly at 40° C. for 1 hour to prepare a polyamic acid solution. The polyamic acid solution was heated to 190° C., heated and stirred for 10 hours, and 125 g of xylene was added to prepare a polyimide solution 1-a (solid content concentration: 30% by weight, weight average molecular weight: 82,900, amine value: 206 mgKOH / g) after imidization.
[0322] (Synthesis Example 1-2 to Synthesis Example 1-3)
[0323] Polyimide solutions 1-b to 1-c were prepared in the same manner as in Synthesis Example 1-1 except that the raw material compositions were as shown in Table 1-1.
[0324] [Table 1-1]
[0325]
[0326] (Production example 1-1)
[0327] 2.7 g of N-12 (0.0105 mol; primary amino group is equivalent to 0.35 mol per 1 mol of ketone group of BTDA) was added to 169.49 g (50 g as solid content) of the polyimide solution 1-a obtained in Synthesis Example 1-1, and 6.0 g of NMP was added for dilution, followed by stirring for 1 hour to obtain a polyimide solution 1-1a.
[0328] The obtained polyimide solution 1-1a was coated on one side of a release PET film (manufactured by Dongshan Film Co., Ltd., trade name: HY-S05, length × width × thickness = 200 mm × 300 mm × 25 μm), dried at 80°C for 15 minutes, and peeled off from the release PET film to prepare a polyimide film 1-1a' with a thickness of 25 μm. The polyimide film 1-1a' was pressed under the conditions of a temperature of 160°C, a pressure of 3.5 MPa, and a time of 60 minutes to obtain a polyimide film 1-1a.
[0329] Various evaluation results of the polyimide film 1-1a are as follows.
[0330] Relative dielectric constant (ε1): 2.7, dielectric loss tangent (Tanδ1): 0.0024, relative dielectric constant (ε2): 2.7, dielectric loss tangent (Tanδ2): 0.0034, moisture absorption: 0.07%, water absorption: 0.6%, Tg: 54℃, 200℃ storage elastic coefficient: 5.0×10 6 Pa, tensile elastic coefficient: 0.7GPa, solder heat resistance (dry): 280℃, solder heat resistance (moisture absorption): 260℃, peel strength: 1.0kN / m or more
[0331] (Production Example 1-2, Production Example 1-3)
[0332] Polyimide solution 1-1b, polyimide solution 1-1c, and polyimide films 1-1b, 1-1c were obtained in the same manner as in Preparation Example 1-1 except that polyimide solution 1-b, polyimide solution 1-c were used instead of polyimide solution 1-a.
[0333] Various evaluation results of the polyimide film 1-1b and the polyimide film 1-1c are as follows.
[0334] <Polyimide film 1-1b>
[0335] Relative dielectric constant (ε1): 2.7, dielectric loss tangent (Tanδ1): 0.0024, relative dielectric constant (ε2): 2.7, dielectric loss tangent (Tanδ2): 0.0034, moisture absorption: 0.07%, water absorption: 0.2%, Tg: 54℃, 200℃ storage elastic coefficient: not determined, tensile elastic coefficient: 0.7GPa
[0336] <Polyimide film 1-1c>
[0337] Relative dielectric constant (ε1): 2.9, dielectric loss tangent (Tanδ1): 0.0028, relative dielectric constant (ε2): 2.9, dielectric loss tangent (Tanδ2): 0.0052, moisture absorption: 0.17%, water absorption: 0.7%, Tg: 106℃, 200℃ storage elastic coefficient: less than 1.0×10 6 Pa, tensile elastic coefficient: 1.4GPa
[0338] [Example 1-1]
[0339] 10 parts by weight of SR-3000 was added to the polyimide solution 1-1a (100 parts by weight of solid content) obtained in Production Example 1-1 to obtain a polyimide composition 1-1. The obtained polyimide composition 1-1 was applied to one side of a release PET film, dried at 80° C. for 15 minutes, and peeled from the release PET film to prepare a polyimide film 1-1′ having a thickness of 25 μm.
[0340] The polyimide film 1 - 1 ′ was heated in an oven at 160° C. for 2 hours to obtain a polyimide film 1 - 1 .
[0341] Various evaluation results of the polyimide film 1-1 are as follows.
[0342] Relative dielectric constant (ε1): 2.6, dielectric loss tangent (Tanδ1): 0.0022
[0343] [Example 1-2 to Example 1-16]
[0344] Each component was blended in the ratio (parts by weight) described in Table 1-2, and polyimide compositions 1-2 to 1-16 were obtained in the same manner as in Example 1-1. In addition, the "DDA composition" in Table 1-2 refers to a dimer diamine composition (the same as in Table 1-3).
[0345] [Table 1-2]
[0346]
[0347] Using the obtained polyimide compositions 1-2 to 1-16, polyimide films 1-2 to 1-16 were prepared in the same manner as in Example 1-1.
[0348] Various evaluation results of polyimide films 1-2 to 1-16 are as follows.
[0349] <Polyimide film 1-2>
[0350] Relative dielectric constant (ε1): 2.7, dielectric loss tangent (Tanδ1): 0.0022, tensile elastic modulus: 0.7GPa, peel strength: 1.4kN / m
[0351] <Polyimide film 1-3>
[0352] Relative dielectric constant (ε1): 2.6, dielectric loss tangent (Tanδ1): 0.0020, relative dielectric constant (ε2): 2.6, dielectric loss tangent (Tanδ2): 0.0021, water absorption: 0.1%, Tg: 54℃, tensile elastic modulus: 0.7GPa, peel strength: 1.4kN / m
[0353] <Polyimide film 1-4>
[0354] Relative dielectric constant (ε1): 2.6, dielectric loss tangent (Tanδ1): 0.0024, tensile elastic modulus: 0.5GPa, peel strength: 1.5kN / m
[0355] <Polyimide film 1-5>
[0356] Relative dielectric constant (ε1): 2.6, dielectric loss tangent (Tanδ1): 0.0022, tensile elastic modulus: 0.7GPa
[0357] <Polyimide film 1-6>
[0358] Relative dielectric constant (ε1): 2.7, dielectric loss tangent (Tanδ1): 0.0023, tensile elastic modulus: 0.1GPa, peel strength: 1.6kN / m
[0359] <Polyimide film 1-7>
[0360] Relative dielectric constant (ε1): 2.6, dielectric loss tangent (Tanδ1): 0.0022, water absorption: 0.29%, tensile elastic modulus: 0.5GPa, peel strength: 1.6kN / m
[0361] <Polyimide film 1-8>
[0362] Relative dielectric constant (ε1): 2.7, dielectric loss tangent (Tanδ1): 0.0021, water absorption: 0.54%, tensile elastic modulus: 0.4GPa, peel strength: 1.3kN / m
[0363] <Polyimide film 1-9>
[0364] Relative dielectric constant (ε1): 2.6, dielectric loss tangent (Tanδ1): 0.0021, water absorption: 0.91%, tensile elastic modulus: 0.3GPa, peel strength: 1.4kN / m
[0365] <Polyimide film 1-10>
[0366] Relative dielectric constant (ε1): 2.7, dielectric loss tangent (Tanδ1): 0.0020, peel strength: 0.7kN / m
[0367] <Polyimide film 1-11>
[0368] Relative dielectric constant (ε1): 2.6, dielectric loss tangent (Tanδ1): 0.0022
[0369] <Polyimide film 1-12>
[0370] Relative dielectric constant (ε1): 2.7, dielectric loss tangent (Tanδ1): 0.0021
[0371] <Polyimide film 1-13>
[0372] Relative dielectric constant (ε1): 2.6, dielectric loss tangent (Tanδ1): 0.0020
[0373] <Polyimide film 1-14>
[0374] Relative dielectric constant (ε1): 2.8, dielectric loss tangent (Tanδ1): 0.0027
[0375] <Polyimide film 1-15>
[0376] Relative dielectric constant (ε1): 2.7, dielectric loss tangent (Tanδ1): 0.0026
[0377] <Polyimide film 1-16>
[0378] Relative dielectric constant (ε1): 2.7, dielectric loss tangent (Tanδ1): 0.0025
[0379] [Reference Example 1-1 to Reference Example 1-18]
[0380] Each component was blended at the ratio (parts by weight) described in Table 1-3, and polyimide compositions 1-17 to 1-34 were obtained in the same manner as in Example 1-1.
[0381] [Table 1-3]
[0382]
[0383] Using the obtained polyimide compositions 1-17 to 1-34, polyimide films 1-17 to 1-34 were prepared in the same manner as in Example 1-1.
[0384] Various evaluation results of polyimide films 1-17 to 1-34 are as follows.
[0385] <Polyimide film 1-17>
[0386] Relative dielectric constant (ε1): 2.7, dielectric loss tangent (Tanδ1): 0.0024, relative dielectric constant (ε2): 2.7, dielectric loss tangent (Tanδ2): 0.0034, water absorption: 0.2%, tensile elastic modulus: 0.9GPa, peel strength: 1.2kN / m
[0387] <Polyimide film 1-18>
[0388] Relative dielectric constant (ε1): 2.9, dielectric loss tangent (Tanδ1): 0.0025, tensile elastic modulus: 0.6GPa, peel strength: 0.4kN / m
[0389] <Polyimide film 1-19>
[0390] Relative dielectric constant (ε1): 2.6, dielectric loss tangent (Tanδ1): 0.0031, tensile elastic modulus: 0.3GPa
[0391] <Polyimide film 1-20>
[0392] Relative dielectric constant (ε1): 2.8, dielectric loss tangent (Tanδ1): 0.0041, tensile elastic modulus: 0.1GPa
[0393] <Polyimide film 1-21>
[0394] Relative dielectric constant (ε1): 2.6, dielectric loss tangent (Tanδ1): 0.0028, tensile elastic modulus: 0.2GPa
[0395] <Polyimide film 1-22>
[0396] Relative dielectric constant (ε1): 2.8, dielectric loss tangent (Tanδ1): 0.0033, tensile elastic modulus: 0.0GPa
[0397] <Polyimide film 1-23>
[0398] Relative dielectric constant (ε1): 2.7, dielectric loss tangent (Tanδ1): 0.0026, tensile elastic modulus: 0.3GPa
[0399] <Polyimide film 1-24>
[0400] Relative dielectric constant (ε1): 2.8, dielectric loss tangent (Tanδ1): 0.0028, tensile elastic modulus: 0.0GPa
[0401] <Polyimide film 1-25>
[0402] Relative dielectric constant (ε1): 2.7, dielectric loss tangent (Tanδ1): 0.0028, tensile elastic modulus: 0.3GPa
[0403] <Polyimide film 1-26>
[0404] Relative dielectric constant (ε1): 2.7, dielectric loss tangent (Tanδ1): 0.0034, tensile elastic modulus: 0.1GPa
[0405] <Polyimide film 1-27>
[0406] Relative dielectric constant (ε1): 2.7, dielectric loss tangent (Tanδ1): 0.0027, tensile elastic modulus: 0.4GPa
[0407] <Polyimide film 1-28>
[0408] Relative dielectric constant (ε1): 2.7, dielectric loss tangent (Tanδ1): 0.0031, tensile elastic modulus: 0.2GPa
[0409] <Polyimide film 1-29>
[0410] Relative dielectric constant (ε1): 2.7, dielectric loss tangent (Tanδ1): 0.0031
[0411] <Polyimide film 1-30>
[0412] Relative dielectric constant (ε1): 2.6, dielectric loss tangent (Tanδ1): 0.0027
[0413] <Polyimide film 1-31>
[0414] Relative dielectric constant (ε1): 2.8, dielectric loss tangent (Tanδ1): 0.0035
[0415] <Polyimide film 1-32>
[0416] Relative dielectric constant (ε1): 2.9, dielectric loss tangent (Tanδ1): 0.0031
[0417] <Polyimide film 1-33>
[0418] Relative dielectric constant (ε1): 3.0, dielectric loss tangent (Tanδ1): 0.0140
[0419] <Polyimide film 1-34>
[0420] Relative dielectric constant (ε1): 2.6, dielectric loss tangent (Tanδ1): 0.0021
[0421] The above results are summarized and the evaluation results of the dielectric properties of the polyimide films 1-1 to 1-34 are shown in Tables 1-4 and 1-5.
[0422] [Table 1-4]
[0423]
[0424] [Table 1-5]
[0425]
[0426] [Example 1-17]
[0427] The components were prepared in the ratio (parts by weight) described in Table 1-2, and the prepared polyimide composition 1-2 was applied to one side of a polyimide film material P1 (manufactured by Toray DuPont, trade name: Kapton 50EN, relative dielectric constant at a frequency of 10 GHz = 3.6, dielectric loss tangent at a frequency of 10 GHz = 0.0084, length × width × thickness = 200 mm × 300 mm × 12 μm) in the same manner as in Example 1-1, and dried at 80° C. for 15 minutes to obtain a cover film 1-17 having an adhesive layer thickness of 25 μm. The warping state of the obtained cover film 1-17 was “good”.
[0428] [Examples 1-18]
[0429] The release PET film was laminated in such a manner as to contact the adhesive layer side of the cover film 1-17, and the film was pressed at a temperature of 160° C. and a pressure of 0.8 MPa for 2 minutes using a vacuum laminator. Thereafter, the polyimide composition 1-2 was applied to the polyimide film material P1 side of the cover film 1-17 in a state where the release PET film was pressed so that the thickness after drying was 25 μm, and dried at 80° C. for 15 minutes. Then, the release PET film was laminated in such a manner as to contact the surface on which the polyimide composition 1-2 was applied and dried, and the film was pressed at a temperature of 160° C. and a pressure of 0.8 MPa for 2 minutes using a vacuum laminator, thereby obtaining a laminate 1-18 including adhesive layers on both sides of the polyimide film material P1.
[0430] [Example 1-19]
[0431] The polyimide composition 1-2 was applied to one side of an electrolytic copper foil having a thickness of 12 μm and dried at 80° C. for 15 minutes to obtain a resin-attached copper foil 1-19 having an adhesive layer thickness of 25 μm. The warpage state of the obtained resin-attached copper foil 1-19 was “good”.
[0432] [Examples 1-20]
[0433] The polyimide composition 1-2 was applied to one side of an electrolytic copper foil having a thickness of 12 μm and dried at 80° C. for 30 minutes to obtain a resin-attached copper foil 1-20 having an adhesive layer thickness of 50 μm. The warpage state of the obtained resin-attached copper foil 1-20 was “good”.
[0434] [Example 1-21]
[0435] The polyimide composition 1-2 was further applied on the surface of the adhesive layer of the resin-attached copper foil 1-19 and dried at 80° C. for 30 minutes to obtain a resin-attached copper foil 1-21 having an adhesive layer with a total thickness of 100 μm. The warpage state of the obtained resin-attached copper foil 1-21 was “good”.
[0436] [Example 1-22]
[0437] The polyimide composition 1-2 was applied on one side of a release PET film, dried at 80° C. for 30 minutes, and peeled from the release PET film to obtain a polyimide film 1-35 having a thickness of 50 μm.
[0438] [Example 1-23]
[0439] A polyimide film 1-2, a polyimide film material P2 (manufactured by DuPont, trade name: Kapton 100-EN, thickness 25 μm, relative dielectric constant at frequency 10 GHz = 3.6, dielectric loss tangent at frequency 10 GHz = 0.0084), a polyimide film 1-2 and an electrolytic copper foil with a thickness of 12 μm are sequentially stacked on an electrolytic copper foil with a thickness of 12 μm, and are pressed together for 2 minutes at a temperature of 160°C and a pressure of 0.8 MPa using a vacuum laminator, and then the temperature is raised from room temperature to 160°C, and heat treated at 160°C for 4 hours to obtain a copper-clad laminate 1-23.
[0440] [Example 1-24]
[0441] The coating film 1-17 is laminated on an electrolytic copper foil having a thickness of 12 μm in such a way that the adhesive layer side of the coating film 1-17 is in contact with the copper foil, and is pressed for 2 minutes at a temperature of 160°C and a pressure of 0.8 MPa using a vacuum laminator, and then the temperature is raised from room temperature to 160°C, and heat treated at 160°C for 2 hours to obtain a copper-clad laminate 1-24.
[0442] [Example 1-25]
[0443] A polyimide film 1-2 is stacked on a rolled copper foil having a thickness of 12 μm, and the stacking is performed in such a manner that the polyimide film material P1 side of the covering film 1-17 is in contact with the polyimide film 1-2, and then a rolled copper foil having a thickness of 12 μm is sequentially stacked on the adhesive layer side of the covering film 1-17. After being pressed for 2 minutes at a temperature of 160°C and a pressure of 0.8 MPa using a vacuum laminator, the temperature is raised from room temperature to 160°C, and heat-treated at 160°C for 2 hours, thereby obtaining a copper-clad laminate 1-25.
[0444] [Example 1-26]
[0445] Two copper foils 1-19 with resin are prepared, and are laminated in a manner such that a polyimide film material P3 (manufactured by DuPont, trade name: Kapton 200-EN, thickness 50 μm, relative dielectric constant at a frequency of 10 GHz = 3.6, dielectric loss tangent at a frequency of 10 GHz = 0.0084) is in contact with the adhesive layer side of the two copper foils 1-19 with resin. After being pressed for 5 minutes using a vacuum laminator at a temperature of 160°C and a pressure of 0.8 MPa, the temperature is raised from room temperature to 160°C, and heat treated at 160°C for 4 hours to obtain a copper-clad laminate 1-26.
[0446] [Example 1-27]
[0447] The polyimide composition 1-2 was applied to the resin layer side of a single-sided copper-clad laminate M1 (manufactured by Nippon Steel Chemical & Materials Co., Ltd., trade name: Espanex MC12-25-00UEM, length × width × thickness = 200 mm × 300 mm × 25 μm), and dried at 80°C for 30 minutes to obtain a copper-clad laminate 1-27 with an adhesive having an adhesive layer thickness of 50 μm. The single-sided copper-clad laminate M1 was laminated in such a way that the resin layer side of the laminate was in contact with the adhesive layer side of the copper-clad laminate 1-27 with an adhesive, and a small precision press was used to press for 120 minutes at a temperature of 160°C and a pressure of 4.0 MPa to obtain a copper-clad laminate 1-27.
[0448] [Example 1-28]
[0449] A polyimide film 1-2 is stacked on the resin layer side of a single-sided copper-clad laminate M1, and further stacked thereon in a manner such that the resin layer side of the single-sided copper-clad laminate M1 is in contact with the polyimide film 1-2, and pressed for 120 minutes at a temperature of 160°C and a pressure of 4.0 MPa using a small precision pressing machine to obtain a copper-clad laminate 1-28.
[0450] [Example 1-29]
[0451] The polyimide composition 1-2 was applied on one surface of a release PET film, dried at 80° C. for 15 minutes, and the adhesive layer was peeled off from the release PET film to obtain a polyimide film 1-36 having a thickness of 15 μm.
[0452] [Example 1-30]
[0453] A double-sided copper-clad laminate M2 (manufactured by Nippon Steel Chemical & Materials Co., Ltd., trade name: Espanex MB12-25-00UEG) was prepared, and a circuit was processed by etching the copper foil on one side to obtain a wiring board 1-1A having a conductor circuit layer formed thereon.
[0454] The copper foil on one side of the double-sided copper-clad laminate M2 is removed by etching to obtain a copper-clad laminate 1-1B.
[0455] The polyimide film 1-2 is sandwiched between the surface on the conductor circuit layer side of the wiring substrate 1-1A and the surface on the resin layer side of the copper-clad laminate 1-1B, and the stacked state is heat-pressed at a temperature of 160°C and a pressure of 4.0 MPa for 120 minutes to obtain a multilayer circuit substrate 1-30.
[0456] [Example 1-31]
[0457] A liquid crystal polymer film (manufactured by Kuraray, trade name: CT-Z, thickness: 50 μm, CTE: 18 ppm / K, heat deformation temperature: 300°C, relative dielectric constant at a frequency of 10 GHz = 3.40, dielectric loss tangent at a frequency of 10 GHz = 0.0022) is prepared as an insulating substrate, and a copper-clad laminate 1-1C having electrolytic copper foil of 18 μm thickness is provided on both sides thereof. Circuit processing is performed on one side of the copper foil by etching to obtain a wiring substrate 1-1C having a conductor circuit layer formed thereon.
[0458] The copper foil on one side of the copper-clad laminate 1-1C is removed by etching to obtain a copper-clad laminate 1-1D.
[0459] The polyimide film 1-2 is sandwiched between the surface on the conductor circuit layer side of the wiring substrate 1-1C and the surface on the insulating base material layer side of the copper-clad laminate 1-1D, and the layers are heat-pressed at a temperature of 160°C and a pressure of 4.0 MPa for 120 minutes to obtain a multilayer circuit substrate 1-31.
[0460] In the following examples, unless otherwise specified, various measurements and evaluations were performed as follows.
[0461] [Evaluation of Dielectric Properties]
[0462] <Silica particles>
[0463] A vector network analyzer (manufactured by Keysight Technologies, trade name: vector network analyzer E8363C) and a relative dielectric constant measuring device manufactured by Kanto Electronics Application Development Co., Ltd. using a resonant cavity perturbation method were used, set to relative dielectric constant measurement mode: TM020, and the relative dielectric constant and dielectric loss tangent of the silica particles at a frequency of 10 GHz were measured. The silica particles were in powder form and filled into a sample tube (inner diameter 1.68 mm, outer diameter 2.28 mm, height 8 cm) for measurement.
[0464] <Resin film>
[0465] Using a vector network analyzer (manufactured by Keysight Technologies, trade name: Vector Network Analyzer E8363C) and a separated dielectric resonator (SPDR), the adhesive sheet that was pressed under the conditions of temperature 160°C, pressure 3.5 MPa, and time 60 minutes was placed under the conditions of temperature: 23°C and humidity: 50% for 24 hours, and then the relative dielectric constant and dielectric loss tangent at a frequency of 20 GHz were measured.
[0466] [Measurement of particle size]
[0467] The particle size was measured by laser diffraction-scattering measurement using a laser diffraction particle size distribution analyzer (Malvern, trade name: Master Sizer 3000) with water as the dispersion medium and a particle refractive index of 1.54.
[0468] [Determination of true specific gravity]
[0469] The true specific gravity was measured by a pycnometer method (liquid phase replacement method) using a continuous automatic powder true density measuring device (manufactured by Seishin Enterprise Co., Ltd., trade name: AUTO TRUE DENSERMAT-7000).
[0470] [Determination of white silica crystal phase]
[0471] Using an X-ray diffraction measuring device (manufactured by Bruker, trade name: D2PHASER), the total area of all peaks originating from SiO2 was calculated based on all diffraction patterns (peak position, peak width and peak intensity) originating from SiO2 in the range of diffraction angle (Cu, Kα) 2θ = 10° to 90°. Secondly, the peak position originating from the white silica crystal phase was determined, the total area of all peaks of the white silica crystal phase was calculated, and the ratio (weight %) to the total area of all peaks originating from SiO2 was obtained. Furthermore, the attribution of each peak was referenced to the database of the International Centre for Diffraction Data (ICDD).
[0472] [Determination of tensile elastic modulus and maximum elongation]
[0473] A tensile test was performed on a test piece (width: 12.7 mm, length: 127 mm) at 50 mm / min using a tensile tester (Tensilon manufactured by Orientec), and the tensile modulus of elasticity and the maximum elongation at 25° C. were determined.
[0474] [Measurement of glass transition temperature (Tg)]
[0475] The adhesive sheet pressed at a temperature of 160°C, a pressure of 3.5 MPa, and a time of 60 minutes was cut into a test piece of 5 mm × 20 mm size, and measured using a dynamic viscoelasticity measuring apparatus (DMA: manufactured by DBM, trade name: E4000F) from 30°C to 300°C at a heating rate of 4°C / min and a frequency of 11 Hz. The temperature at which the elastic modulus change (tanδ) is the largest is defined as the glass transition temperature.
[0476] [Evaluation of film retention]
[0477] The film retention is evaluated by the following procedure. Cut the adhesive sheet into a test piece with a width of 20 mm and a length of 20 mm, bend it along the diagonal line to form a crease, open it and observe the state of the film. At this time, the film with no cracks after opening the test piece with the crease is rated as "good", and the film with partial cracks is rated as "unacceptable".
[0478] [Solder heat resistance test (dry)]
[0479] Prepare the following printed circuit board: etch and remove one of the copper foils of the double-sided copper-clad laminate (manufactured by Nippon Steel Chemical & Materials Co., Ltd., trade name: Espanex MB12-25-12UEG), and process the other copper foil to form a circuit with wiring width / wiring spacing (L / S) = 1mm / 1mm. Place an adhesive sheet on the wiring of the printed circuit board, and laminate a polyimide film (manufactured by Toray DuPont Co., Ltd., trade name: Kapton 50EN-S) on the opposite side of the adhesive sheet in contact with the printed circuit board, and then press at a temperature of 160°C, a pressure of 3.5MPa, and a time of 60 minutes. After drying the test piece with copper foil at 105°C, immerse it in a solder bath set to each evaluation temperature for 10 seconds, observe its bonding state, and confirm whether there are defects such as foaming, expansion, and peeling. Heat resistance is expressed by the upper limit temperature at which no malfunction occurs. For example, "320° C." means that no malfunction was observed in the evaluation in a solder bath at 320° C.
[0480] [Solder heat resistance test (moisture absorption)]
[0481] The following printed circuit board was prepared: the copper foil on one side of a double-sided copper-clad laminate (manufactured by Nippon Steel Chemical & Materials Co., Ltd., trade name: Espanex MB12-25-12UEG) was etched away, and the other copper foil was processed into a circuit to form a circuit with a wiring width / wiring spacing (L / S) = 1 mm / 1 mm. An adhesive sheet was placed on the wiring of the printed circuit board, and a polyimide film (manufactured by Toray DuPont Co., Ltd., trade name: Kapton 50EN-S) was laminated on the opposite side of the adhesive sheet to the surface in contact with the printed circuit board, and then pressed under the conditions of temperature: 160°C, pressure: 3.5 MPa, and time: 60 minutes. After the test piece with copper foil was placed at 40°C and relative humidity: 80% for 72 hours, it was immersed in a solder bath set to each evaluation temperature for 10 seconds, and its bonding state was observed to confirm whether there were defects such as foaming, expansion, and peeling. Heat resistance is expressed by the upper limit temperature at which no malfunction occurs. For example, "260° C." means that no malfunction was observed in the evaluation in a solder bath at 260° C.
[0482] [Determination of peel strength]
[0483] After cutting a double-sided copper-clad laminate (manufactured by Nippon Steel Chemical & Materials Co., Ltd., trade name: Espanex MB12-25-12UEG) into a width of 50 mm and a length of 100 mm, an adhesive sheet was placed on the copper foil side of the sample after etching away the copper foil on one side, and a polyimide film (manufactured by Toray DuPont Co., Ltd., trade name: Kapton 50EN-S) was stacked on the adhesive sheet, and pressed under the conditions of temperature: 160°C, pressure: 3.5 MPa, and time: 60 minutes. The laminate was cut into a test piece with a width of 5 mm, and a tensile tester (manufactured by Toyo Seiki Co., Ltd., trade name: Strograph VE) was used to stretch the test piece in the 90° direction at a speed of 50 mm / min, and the peel strength between the adhesive layer and the copper foil at this time was measured.
[0484] [Evaluation method of flame retardancy]
[0485] A polyimide film (manufactured by Toray DuPont Co., Ltd., trade name: Kapton 50EN-S) was laminated on both sides of the adhesive sheet and pressed under the conditions of temperature: 160°C, pressure: 3.5MPa, and time: 60 minutes. The sample was cut into 200mm±5mm×50mm±1mm, rounded in a cylindrical shape with a diameter of about 12.7mm and a length of 200mm±5mm, and a test piece according to the UL94VTM standard was made and a combustion test was performed. The case where the judgment standard of VTM-0 was achieved was set as "good". The case where the judgment standard of VTM-1 was achieved was set as "acceptable", and the case where the judgment standard of VTM-1 was not achieved was set as "unacceptable".
[0486] (Synthesis example 2-1)
[0487] 55.51 g of BTDA (0.1721 mol), 94.49 g of DDA2 (0.1735 mol), 210 g of NMP and 140 g of xylene were placed in a 1000 ml separable flask and mixed thoroughly at 40° C. for 1 hour to prepare a polyamic acid solution. The polyamic acid solution was heated to 190° C., heated and stirred for 10 hours, and 125 g of xylene was added to prepare a polyimide solution 2-1 (solid content: 30% by weight, weight average molecular weight: 80,900) after imidization.
[0488] [Example 2-1]
[0489] 1.09 g of N-12 and 7.50 g of filler 1 were mixed with 100 g of the polyimide solution 2-1 prepared in Synthesis Example 2-1, and xylene was added to dilute and stir the mixture so that the solid content became 30 wt %, thereby preparing a polyimide varnish 2-1a.
[0490] [Example 2-2 to Example 2-8]
[0491] Polyimide varnishes 2-2a to 2-8a were prepared in the same manner as in Example 2-1 except that the blending amounts of the filler 1 and the filler 2 were changed as shown in Table 2-1.
[0492] [Comparative Example 2-1]
[0493] A polyimide varnish 2-9a was prepared in the same manner as in Example 2-1 except that the filler 1 was not blended.
[0494] [Table 2-1]
[0495]
[0496] [Example 2-9]
[0497] The polyimide varnish 2-1a prepared in Example 2-1 was applied to one surface of a release-treated PET film, dried at 80° C. for 15 minutes, and then peeled off to prepare an adhesive sheet 2-1b (thickness: 25 μm).
[0498] The various evaluation results of the adhesive sheet 2-1b are as follows.
[0499] Relative dielectric constant: 2.7, dielectric loss tangent: 0.0015, tensile elastic modulus: 0.6GPa, maximum elongation: 165%, Tg: 56℃, film retention: good, solder heat resistance test (dry): 320℃, solder heat resistance test (moisture absorption): 260℃, peel strength: 1.8kN / m, flame retardancy: good
[0500] [Example 2-10]
[0501] Using the polyimide varnish 2-2a, an adhesive sheet 2-2b was prepared in the same manner as in Example 2-9.
[0502] Various evaluation results of the adhesive sheet 2-2b are as follows.
[0503] Relative dielectric constant: 2.9, dielectric loss tangent: 0.0013, tensile elastic modulus: 0.5GPa, maximum elongation: 77%, Tg: 56℃, film retention: good, solder heat resistance test (dry): 320℃, solder heat resistance test (moisture absorption): 260℃, peel strength: 1.8kN / m, flame retardancy: good
[0504] [Example 2-11]
[0505] Using the polyimide varnish 2-3a, an adhesive sheet 2-3b was prepared in the same manner as in Example 2-9.
[0506] Various evaluation results of the adhesive sheet 2-3b are as follows.
[0507] Relative dielectric constant: 2.8, dielectric loss tangent: 0.0012, tensile elastic modulus: 0.6GPa, maximum elongation: 59%, Tg: 56℃, film retention: good, solder heat resistance test (dry): 320℃, solder heat resistance test (moisture absorption): 270℃, peel strength: 1.8kN / m, flame retardancy: good
[0508] [Example 2-12]
[0509] Using the polyimide varnish 2-4a, an adhesive sheet 2-4b was prepared in the same manner as in Example 2-9.
[0510] Various evaluation results of the adhesive sheet 2-4b are as follows.
[0511] Relative dielectric constant: 2.8, dielectric loss tangent: 0.0011, tensile elastic modulus: 0.8GPa, maximum elongation: 31%, Tg: 56℃, film retention: good, solder heat resistance test (dry): 320℃, solder heat resistance test (moisture absorption): 280℃, peel strength: 1.9kN / m, flame retardancy: good
[0512] [Example 2-13]
[0513] Using the polyimide varnish 2-5a, an adhesive sheet 2-5b was prepared in the same manner as in Example 2-9.
[0514] Various evaluation results of the adhesive sheet 2-5b are as follows.
[0515] Relative dielectric constant: 2.8, dielectric loss tangent: 0.0016, tensile elastic modulus: 0.8GPa, maximum elongation: 29%, Tg: 56℃, film retention: good, solder heat resistance test (dry): 320℃, solder heat resistance test (moisture absorption): 270℃, peel strength: 1.9kN / m, flame retardancy: good
[0516] [Example 2-14]
[0517] Using the polyimide varnish 2-6a, an adhesive sheet 2-6b was prepared in the same manner as in Example 2-9.
[0518] Various evaluation results of the adhesive sheet 2-6b are as follows.
[0519] Relative dielectric constant: 2.7, dielectric loss tangent: 0.0015, tensile elastic modulus: 0.6GPa, maximum elongation: 169%, Tg: 56℃, film retention: good, solder heat resistance test (dry): 320℃, solder heat resistance test (moisture absorption): 260℃, peel strength: 1.7kN / m, flame retardancy: good
[0520] [Example 2-15]
[0521] Using the polyimide varnish 2-7a, an adhesive sheet 2-7b was prepared in the same manner as in Example 2-9.
[0522] Various evaluation results of the adhesive sheet 2-7b are as follows.
[0523] Relative dielectric constant: 2.8, dielectric loss tangent: 0.0012, tensile elastic modulus: 0.7GPa, maximum elongation: 28%, Tg: 56℃, film retention: good, solder heat resistance test (dry): 320℃, solder heat resistance test (moisture absorption): 280℃, peel strength: 1.8kN / m, flame retardancy: good
[0524] [Example 2-16]
[0525] Using the polyimide varnish 2-8a, an adhesive sheet 2-8b was prepared in the same manner as in Example 2-9.
[0526] Various evaluation results of the adhesive sheet 2-8b are as follows.
[0527] Relative dielectric constant: 2.6, dielectric loss tangent: 0.0016, tensile elastic modulus: 0.5GPa, maximum elongation: 177%, Tg: 56℃, film retention: good, solder heat resistance test (dry): 320℃, solder heat resistance test (moisture absorption): 260℃, peel strength: 1.7kN / m, flame retardancy: acceptable
[0528] [Comparative Example 2-2]
[0529] Using the polyimide varnish 2-9a, an adhesive sheet 2-9b was prepared in the same manner as in Example 2-9.
[0530] Various evaluation results of the adhesive sheet 2-9b are as follows.
[0531] Relative dielectric constant: 2.6, dielectric loss tangent: 0.0017, tensile elastic modulus: 0.4GPa, maximum elongation: 197%, Tg: 56℃, film retention: good, solder heat resistance test (dry): 320℃, solder heat resistance test (moisture absorption): 220℃, peel strength: 1.6kN / m, flame retardancy: not acceptable
[0532] The above results are summarized and shown in Table 2-2.
[0533] [Table 2-2]
[0534]
[0535] According to Table 2-2, it is confirmed that the dielectric properties and solder heat resistance temperature (moisture absorption) of the adhesive sheets 2-1b to 2-8b of Examples 2-9 to 2-16 to which fillers 1 and fillers 2 are added are improved compared to the adhesive sheet 2-9b of Comparative Example 2-2. Based on such results, the adhesive sheet as the resin film of the present embodiment can be expected to reduce the transmission loss in the high frequency band of 20 GHz, for example. In addition, it is confirmed that the adhesive sheets 2-1b to 2-8b of Examples 2-9 to 2-16 to which fillers 1 and fillers 2 are added have improved hygroscopic solder heat resistance, peel strength and flame retardancy while maintaining flexibility or film retention compared to the adhesive sheet 2-9b of Comparative Example 2-2.
[0536] As described above, as shown in each of the Examples, by adding white silica particles to DDA / BTDA-based polyimide, a clear effect of reducing the dielectric loss tangent can be observed.
[0537] In addition, flame retardancy was evaluated using a layer structure of polyimide film / adhesive layer / polyimide film. As a result, it was confirmed that the adhesive layer containing white silica particles exhibited flame retardancy at or above the VTM-1 level.
[0538] Furthermore, the adhesive sheets obtained in each example maintained the shape of a film in the practical range of the blending amount of white silica particles, and the adhesion to polyimide or copper was also improved. Although the mechanism of the improved adhesion cannot be elucidated, it is speculated that the improvement in the elastic modulus of the adhesive sheet may contribute.
[0539] The solder heat resistance (drying and / or moisture absorption) of the adhesive sheet obtained in the examples was equal to or better than that of the comparative example without blending white silica particles, showing preferable characteristics as an adhesive for high-frequency multilayer FPC.
[0540] From the above results, it was confirmed that the resin film of the present embodiment can be suitably used as a material for a high-frequency compatible flexible printed circuit board.
[0541] In the following examples, unless otherwise specified, various measurements and evaluations were performed as follows.
[0542] [Evaluation of Dielectric Properties]
[0543] <Liquid crystal polymer filler>
[0544] A dimethylacetamide dispersion of a liquid crystal polymer filler adjusted to 30% by weight of solid content was applied to the smooth surface of the copper foil and dried at 120° C. for 10 minutes. Thereafter, the temperature was gradually raised from 200° C. to 360° C. over 10 minutes to etch and remove the copper foil of the obtained laminate, thereby obtaining a liquid crystal polymer film.
[0545] Using a vector network analyzer (manufactured by Keysight Technologies, trade name: Vector Network Analyzer E8363C) and a separated dielectric resonator (SPDR resonator), the obtained liquid crystalline polymer film was placed under temperature: 23°C and humidity: 50% for 24 hours, and then the relative dielectric constant and dielectric loss tangent at a frequency of 10 GHz were measured.
[0546] <Resin film>
[0547] Using a vector network analyzer (manufactured by Keysight Technologies, trade name: Vector Network Analyzer E8363C) and an SPDR resonator, the resin film that was pressed at a temperature of 160°C, a pressure of 3.5 MPa, and a time of 60 minutes was placed at a temperature of 23°C and a humidity of 50% for 24 hours, and then the relative dielectric constant and dielectric loss tangent at a frequency of 20 GHz were measured.
[0548] [Determination of tensile elastic modulus and maximum elongation]
[0549] The tensile modulus and the maximum elongation were measured by the following procedure. First, a test piece (width 12.7 mm×length 127 mm) was prepared from a resin film using a tensile tester (Tensilon manufactured by Orientec). The test piece was used to perform a tensile test at 50 mm / min to obtain the tensile modulus and the maximum elongation at 25°C.
[0550] [Measurement of glass transition temperature (Tg)]
[0551] The glass transition temperature (Tg) is obtained by cutting a resin film pressed at a temperature of 160°C, a pressure of 3.5 MPa, and a time of 60 minutes into a test piece of 5 mm × 20 mm, and using a dynamic viscoelasticity measuring apparatus (DMA: manufactured by DBM, trade name: E4000F) to measure the temperature from 30°C to 300°C at a heating rate of 4°C / min and a frequency of 11 Hz. The temperature at which the elastic modulus change (tanδ) is the largest is defined as the glass transition temperature.
[0552] [Evaluation of film retention]
[0553] The film retention is evaluated by the following procedure. The resin film is cut into a test piece with a width of 20 mm and a length of 20 mm, and after being folded along the diagonal line to form a crease, the film is opened and the state of the film is observed. At this time, the film with no cracks even after the test piece with the crease is opened is rated as "good", and the film with partial cracks is rated as "unacceptable".
[0554] [Solder heat resistance test (dry)]
[0555] Prepare the following printed substrate: a polyimide copper-clad laminate (manufactured by Nippon Steel Chemical & Materials Co., Ltd., trade name: Espanex MB12-25-12UEG) is processed for circuit processing to form a circuit with wiring width / wiring spacing (L / S) = 1 mm / 1 mm. A resin film is placed on the wiring of the printed substrate, and a polyimide film (manufactured by Toray DuPont Co., Ltd., trade name: Kapton 50EN-S) is laminated on the opposite side of the resin film to the surface in contact with the printed substrate, and then pressed under the conditions of temperature: 160°C, pressure: 3.5 MPa, and time: 60 minutes. After drying the test piece with copper foil at 105°C, it is immersed in a solder bath set to each evaluation temperature for 10 seconds, and its bonding state is observed to confirm whether there are defects such as foaming, expansion, and peeling. Heat resistance is expressed by the upper limit temperature at which no malfunction occurs. For example, "320° C." means that no malfunction was observed in the evaluation in a solder bath at 320° C.
[0556] [Solder heat resistance test (moisture absorption)]
[0557] The following printed substrate was prepared: a polyimide copper-clad laminate (manufactured by Nippon Steel Chemical & Materials Co., Ltd., trade name: Espanex MB12-25-12UEG) was processed for circuit processing to form a circuit with a wiring width / wiring spacing (L / S) = 1 mm / 1 mm. A resin film was placed on the wiring of the printed substrate, and a polyimide film (manufactured by Toray DuPont Co., Ltd., trade name: Kapton 50EN-S) was laminated on the opposite side of the resin film to the surface in contact with the printed substrate, and then pressed under the conditions of temperature: 160°C, pressure: 3.5 MPa, and time: 60 minutes. After the test piece with copper foil was placed at 40°C and relative humidity of 80% for 72 hours, it was immersed in a solder bath set to each evaluation temperature for 10 seconds, and its bonding state was observed to confirm whether there were defects such as foaming, expansion, and peeling. Heat resistance is expressed by the upper limit temperature at which no malfunction occurs. For example, "260° C." means that no malfunction was observed in the evaluation in a solder bath at 260° C.
[0558] [Determination of peel strength]
[0559] The determination of peel strength is carried out by the following method. The copper foil on one side of a double-sided polyimide copper-clad laminate (manufactured by Nippon Steel Chemical & Materials Co., Ltd., trade name: Espanex MB12-25-12UEG) cut into a width of 50 mm and a length of 100 mm is etched, and a resin film is placed on the remaining other copper foil side, and a polyimide film (manufactured by Toray DuPont Co., Ltd., trade name: Kapton 50EN-S) is laminated on the opposite side of the resin film to the copper-clad laminate, and pressed under the conditions of temperature: 160°C, pressure: 3.5MPa, and time: 60 minutes. The laminate is cut into a test piece with a width of 5mm, and a tensile tester (manufactured by Toyo Seiki Seisakusho, Strograph VE) is used to stretch the test piece at a speed of 50mm / min in the 90° direction, and the peel strength of the resin film and the copper foil as the adhesive layer at this time is measured.
[0560] [Evaluation method of flame retardancy]
[0561] The evaluation of flame retardancy is carried out by the following method. A polyimide film (manufactured by Toray DuPont Co., Ltd., trade name: Kapton 50EN-S) is laminated on both sides of a resin film laminated in a manner of 100 μm with four sheets, and pressed under the conditions of temperature: 160°C, pressure: 3.5 MPa, and time: 60 minutes. The sample is cut into 200mm±5mm×50mm±1mm, rounded in a cylindrical manner with a diameter of about 12.7mm and a length of 200mm±5mm, and a test piece according to the UL94VTM standard is made and a combustion test is carried out. If the time until the fire is 0 seconds to 5 seconds, it is set to "◎" (excellent), if it is 6 seconds to 10 seconds, it is set to "○" (good), if it is 11 seconds to 20 seconds, it is set to "△" (allowable), and the case exceeding 21 seconds is set to "×" (unacceptable).
[0562] [Synthesis example 3-1]
[0563] 55.51 g of BTDA (0.1721 mol), 94.49 g of DDA2 (0.1735 mol), 210 g of NMP and 140 g of xylene were placed in a 1000 ml separable flask and mixed thoroughly at 40° C. for 1 hour to prepare a polyamic acid solution. The polyamic acid solution was heated to 190° C., heated and stirred for 10 hours, and 125 g of xylene was added to prepare a polyimide solution 3-1 (solid content: 30% by weight, weight average molecular weight: 80,900) after imidization.
[0564] [Example 3-1]
[0565] 1.09 g of N-12 and 7.50 g of LCP filler were mixed with 100 g of the polyimide solution 3-1 prepared in Synthesis Example 3-1, and xylene was added to dilute and stir the mixture so that the solid content became 30 wt %, thereby preparing a polyimide varnish 3-1a.
[0566] [Example 3-2 to Example 3-4]
[0567] Polyimide varnishes 3-2a to 3-4a were prepared in the same manner as in Example 3-1 except that the amount of the LCP filler was changed as shown in Table 3-1.
[0568] [Examples 3-5]
[0569] 1.09 g of N-12, 7.50 g of LCP filler and 7.50 g of flame retardant 1 were mixed with 100 g of polyimide solution 3-1 prepared in Synthesis Example 3-1, and xylene was added to dilute and stir to give a solid content of 30 wt %, thereby preparing polyimide varnish 3-5a.
[0570] [Example 3-6 to Example 3-7]
[0571] Polyimide varnishes 3-6a to 3-7a were prepared in the same manner as in Example 3-5 except that the amount of the LCP filler was changed as shown in Table 3-1.
[0572] [Example 3-8 to Example 3-10]
[0573] Polyimide varnishes 3-8a to 3-10a were prepared in the same manner as in Example 3-5 except that flame retardant 2 was used in the amount of formulation shown in Table 3-1 instead of flame retardant 1 and the LCP filler was formulated as shown in Table 3-1.
[0574] [Comparative Example 3-1]
[0575] A polyimide varnish 3-11a was prepared in the same manner as in Example 3-1 except that the LCP filler was not blended.
[0576] [Comparative Example 3-2]
[0577] A polyimide varnish 3-12a was prepared in the same manner as in Example 3-5 except that the LCP filler was not blended.
[0578] [Table 3-1]
[0579]
[0580] [Example 3-11]
[0581] The polyimide varnish 3-1a prepared in Example 3-1 was applied to one surface of a release-treated PET film, dried at 80° C. for 15 minutes, and then peeled off to prepare a resin film 3-1b (thickness: 25 μm).
[0582] Various evaluation results of the resin film 3-1b are as follows.
[0583] Relative dielectric constant: 2.7, dielectric loss tangent: 0.0015, tensile elastic modulus: 0.6GPa, maximum elongation: 131%, Tg: 54℃, film retention: good, solder heat resistance test (dry): 320℃, solder heat resistance test (moisture absorption): 260℃, peel strength: 1.6kN / m, flame retardancy: ○
[0584] [Example 3-12]
[0585] Using the polyimide varnish 3-2a, a resin film 3-2b was prepared in the same manner as in Example 3-11.
[0586] Various evaluation results of the resin film 3-2b are as follows.
[0587] Relative dielectric constant: 2.7, dielectric loss tangent: 0.0014, tensile elastic modulus: 0.7GPa, maximum elongation: 80%, Tg: 54℃, film retention: good, solder heat resistance test (dry): 320℃, solder heat resistance test (moisture absorption): 260℃, peel strength: 1.5kN / m, flame retardancy: ○
[0588] [Example 3-13]
[0589] Using the polyimide varnish 3-3a, a resin film 3-3b was prepared in the same manner as in Example 3-11.
[0590] Various evaluation results of the resin film 3 - 3 b are as follows.
[0591] Relative dielectric constant: 2.8, dielectric loss tangent: 0.0014, tensile elastic modulus: 0.7GPa, maximum elongation: 38%, Tg: 58℃, film retention: good, solder heat resistance test (dry): 320℃, solder heat resistance test (moisture absorption): 270℃, peel strength: 1.2kN / m, flame retardancy: ○
[0592] [Examples 3-14]
[0593] Using the polyimide varnish 3-4a, a resin film 3-4b was prepared in the same manner as in Example 3-11.
[0594] Various evaluation results of the resin film 3 - 4b are as follows.
[0595] Relative dielectric constant: 2.9, dielectric loss tangent: 0.0013, tensile elastic modulus: 0.8GPa, maximum elongation: 18%, Tg: 58℃, film retention: good, solder heat resistance test (dry): 320℃, solder heat resistance test (moisture absorption): 270℃, peel strength: 1.2kN / m, flame retardancy: ○
[0596] [Example 3-15]
[0597] Using the polyimide varnish 3-5a, a resin film 3-5b was prepared in the same manner as in Example 3-11.
[0598] Various evaluation results of the resin film 3 - 5b are as follows.
[0599] Relative dielectric constant: 2.7, dielectric loss tangent: 0.0016, tensile elastic modulus: 0.5GPa, maximum elongation: 100%, Tg: 54℃, film retention: good, solder heat resistance test (dry): 320℃, solder heat resistance test (moisture absorption): 270℃, peel strength: 2.0kN / m, flame retardancy: ◎
[0600] [Example 3-16]
[0601] Using the polyimide varnish 3-6a, a resin film 3-6b was prepared in the same manner as in Example 3-11.
[0602] Various evaluation results of the resin film 3-6b are as follows.
[0603] Relative dielectric constant: 2.8, dielectric loss tangent: 0.0015, tensile elastic modulus: 0.7GPa, maximum elongation: 33%, Tg: 58℃, film retention: good, solder heat resistance test (dry): 320℃, solder heat resistance test (moisture absorption): 270℃, peel strength: 1.3kN / m, flame retardancy: ◎
[0604] [Example 3-17]
[0605] Using the polyimide varnish 3-7a, a resin film 3-7b was prepared in the same manner as in Example 3-11.
[0606] Various evaluation results of the resin film 3-7b are as follows.
[0607] Relative dielectric constant: 2.8, dielectric loss tangent: 0.0014, tensile elastic modulus: 0.7GPa, maximum elongation: 11%, Tg: 58℃, film retention: good, solder heat resistance test (dry): 320℃, solder heat resistance test (moisture absorption): 280℃, peel strength: 0.9kN / m, flame retardancy: ◎
[0608] [Example 3-18]
[0609] Using the polyimide varnish 3-8a, a resin film 3-8b was prepared in the same manner as in Example 3-11.
[0610] Various evaluation results of the resin film 3-8b are as follows.
[0611] Relative dielectric constant: 2.7, dielectric loss tangent: 0.0015, tensile elastic modulus: 0.5GPa, maximum elongation: 114%, Tg: 54℃, film retention: good, solder heat resistance test (dry): 320℃, solder heat resistance test (moisture absorption): 280℃, peel strength: 1.4kN / m, flame retardancy: ◎
[0612] [Example 3-19]
[0613] Using the polyimide varnish 3-9a, a resin film 3-9b was prepared in the same manner as in Example 3-11.
[0614] Various evaluation results of the resin film 3-9b are as follows.
[0615] Relative dielectric constant: 2.8, dielectric loss tangent: 0.0014, tensile elastic modulus: 0.6GPa, maximum elongation: 52%, Tg: 56℃, film retention: good, solder heat resistance test (dry): 320℃, solder heat resistance test (moisture absorption): 280℃, peel strength: 1.0kN / m, flame retardancy: ◎
[0616] [Example 3-20]
[0617] Using the polyimide varnish 3-10a, a resin film 3-10b was prepared in the same manner as in Example 3-11.
[0618] Various evaluation results of the resin film 3-10b are as follows.
[0619] Relative dielectric constant: 2.9, dielectric loss tangent: 0.0013, tensile elastic modulus: 0.6GPa, maximum elongation: 22%, Tg: 56℃, film retention: good, solder heat resistance test (dry): 320℃, solder heat resistance test (moisture absorption): 290℃, peel strength: 0.7kN / m, flame retardancy: ◎
[0620] [Comparative Example 3-3]
[0621] Using the polyimide varnish 3-11a, a resin film 3-11b was prepared in the same manner as in Example 3-11.
[0622] Various evaluation results of the resin film 3-11b are as follows.
[0623] Relative dielectric constant: 2.6, dielectric loss tangent: 0.0017, tensile elastic modulus: 0.4GPa, maximum elongation: 197%, Tg: 56℃, film retention: good, solder heat resistance test (dry): 320℃, solder heat resistance test (moisture absorption): 220℃, peel strength: 1.6kN / m, flame retardancy: ×
[0624] [Comparative Examples 3-4]
[0625] Using the polyimide varnish 3-12a, a resin film 3-12b was prepared in the same manner as in Example 3-11.
[0626] Various evaluation results of the resin film 3-12b are as follows.
[0627] Relative dielectric constant: 2.6, dielectric loss tangent: 0.0018, tensile elastic modulus: 0.8GPa, maximum elongation: 226%, Tg: 56℃, film retention: good, solder heat resistance test (dry): 320℃, solder heat resistance test (moisture absorption): 280℃, peel strength: 1.7kN / m, flame retardancy: △
[0628] The above results are summarized and shown in Table 3-2.
[0629] [Table 3-2]
[0630]
[0631] According to Table 3-2, it is confirmed that the dielectric loss tangent, flame retardancy and solder heat resistance temperature (moisture absorption) of resin films 3-1b to 3-4b of Examples 3-11 to 3-14 to which LCP fillers are added are improved compared to resin film 3-11b of Comparative Example 3-3. As the amount of LCP filler added, which has a lower dielectric loss tangent than DDA-based thermoplastic polyimide, increases, the dielectric loss tangent of the resin film decreases. In addition, by blending LCP fillers with a high aromatic ring concentration in the easily flammable DDA-based thermoplastic polyimide, an excellent flame retardant effect is exhibited. It can be further considered that by adding LCP fillers, the hygroscopic components are reduced and the elastic modulus is increased, thereby improving solder heat resistance.
[0632] In addition, the resin films 3-1b to 3-4b maintain film properties, and the bonding strength also exceeds 0.6 kN / m generally required for the manufacture of flexible printed wiring boards, so the resin film of this embodiment is preferably made into a flexible printed wiring board using a high frequency band of 10 GHz or more. The elongation of DDA-based thermoplastic polyimide is large, so the film properties can be maintained even if LCP filler is added. Furthermore, Tg is sufficiently low for the pressing temperature, so it is believed that the resin follows the fine concavo-convex of the copper foil surface, and the carbonyl group of BTDA used as an acid anhydride is used to ensure adhesion.
[0633] In addition, according to Table 3-2, compared with the resin film 3-12b of the comparison example 3-4, the dielectric loss tangent of the resin films 3-5b to 3-10b of Examples 3-15 to 3-20 to which LCP filler is added is reduced, and the flame retardancy is greatly improved, for example, they are preferably used as high-frequency flexible printed wiring board materials corresponding to the increasingly thick film of the dielectric layer.
[0634] It is believed that in the combination of only DDA-based thermoplastic polyimide and phosphorus-based flame retardant, the carbon formation effect of the phosphorus-based flame retardant cannot be fully manifested in most cases due to the low concentration of aromatic rings in the DDA-based thermoplastic polyimide. In contrast, as shown in Examples 3-15 to 3-20, by using a combination of DDA-based thermoplastic polyimide, LCP filler and phosphorus-based flame retardant, the aromatic ring concentration in the composition becomes higher, resulting in a greater flame retardant effect of the phosphorus-based flame retardant.
[0635] As mentioned above, although embodiment of this invention was described in detail for the purpose of illustration, this invention is not limited to the said embodiment, Various deformation|transformation is possible.
Claims
1. A polyimide composition, characterized in that: Contains the following components (A) and (B); (A) component: a polyimide obtained by reacting a tetracarboxylic anhydride component with a diamine component, wherein the diamine component contains a dimer diamine composition having as a main component a dimer diamine in which both terminal carboxylic acid groups of a dimer acid are substituted with a primary aminomethyl group or an amino group in an amount of 40 mol % or more relative to the total diamine components, and (B) component: an aromatic condensed phosphate ester, and The weight ratio of the component (B) to the component (A) is in the range of 0.05 to 0.
7.
2. The polyimide composition according to claim 1, characterized in that The weight ratio of the component (B) to the component (A) is in the range of 0.2 to 0.
5.
3. The polyimide composition according to claim 1, characterized in that The weight ratio of phosphorus derived from the component (B) to the component (A) is in the range of 0.01 to 0.
1. 4 . The polyimide composition according to claim 1 , wherein a weight ratio of phosphorus derived from the component (B) to the dimer diamine composition in the component (A) is within a range of 0.01 to 0.
15.
5. The polyimide composition according to claim 1, characterized in that: Furthermore, it contains an amino compound having at least two primary amino groups as functional groups.
6. A resin film, characterized in that: A polyimide layer is included, wherein the polyimide layer contains the following components (A) and (B); (A) component: a polyimide obtained by reacting a tetracarboxylic anhydride component with a diamine component, wherein the diamine component contains a dimer diamine composition having as a main component a dimer diamine in which both terminal carboxylic acid groups of a dimer acid are substituted with a primary aminomethyl group or an amino group in an amount of 40 mol % or more relative to the total diamine components, and (B) component: an aromatic condensed phosphate ester, and The weight ratio of the component (B) to the component (A) is in the range of 0.05 to 0.
7.
7. A laminated body, characterized in that: A substrate and an adhesive layer laminated on at least one surface of the substrate, wherein The adhesive layer includes the resin film according to claim 6 .
8. A covering film, characterized in that: The invention comprises a covering film material layer and an adhesive layer laminated on the covering film material layer, wherein: The adhesive layer includes the resin film according to claim 6 .
9. A copper foil with resin, characterized in that: It is formed by laminating an adhesive layer and a copper foil, wherein: The adhesive layer includes the resin film according to claim 6 .
10. A metal-clad laminate, characterized in that: The invention comprises an insulating resin layer and a metal layer laminated on at least one surface of the insulating resin layer, wherein: At least one layer of the insulating resin layer comprises the resin film according to claim 6.
11. A circuit board obtained by subjecting the metal layer of the metal-clad laminate according to claim 10 to wiring processing.
Citation Information
Patent Citations
Automatic focusing device
JP1987067509A
Variable equalizer
JP1987095013A
Base board for circuit board and printed circuit board using the same
JP2001185853A
Crosslinked polyimide resin, adhesive resin composition and cured product thereof, cover lay film and circuit board
JP2013001730A
Copper foil with resin, copper-clad laminate, printed wiring board and multilayer wiring board
JP2017119361A